Holocene development and climatic sensitivity of an Amazonian peatland pole forest: Nueva York, Peru - Christine M. Åkesson; Katherine H. Roucoux; Arnoud Boom; Greta C. Dargie; Jhon del Aguila-Pasquel; Gerardo Flores; Pauline Gulliver; William Hiles; Timothy R. Baker; Frederick C. Draper; Adam Hastie; Eurídice N. Honorio Coronado; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Managing the Unmanageable: Understanding the Competing Effects of Salinity and Nutrient Loading on Estuarine Water Quality - Marcus W. Beck; Edward T. Sherwood; Rebecca R. Murphy; Kerry Flaherty-Walia; Qian Zhang; Blake A. Simmons; Maya C. Burke (Estuaries and Coasts, 2026)
Changing climatic conditions that can alter physical characteristics of surface waters may limit the effectiveness of conventional approaches to nutrient management. This study evaluated the competing effects of nutrient loads and changing salinity on chlorophyll-a dynamics in Tampa Bay (Florida, USA). This estuary has demonstrated long-term recovery of water quality primarily through wastewater infrastructure improvements, whereas a gradual freshening of the bay over the last few decades may compromise future management efforts to protect water quality. The relative effects of loading and salinity over a forty-year time period were evaluated using normalized predictions from Generalized Additive Models (GAMs). All bay segments showed a gradually increasing influence of reduced salinity on chlorophyll-a. Old Tampa Bay in the northwest also showed an increasing influence of nutrient loading. Simulation scenarios using the GAMs assessed the relative likelihood of exceeding regulatory chlorophyll-a standards under future salinity conditions. All bay segments showed an increased likelihood of exceeding regulatory standards, particularly in Old Tampa Bay where likelihood increased by ~ 16% over a fifty-year simulation. The results suggested that current nutrient loads should be substantially reduced below the federally-recognized Total Maximum Daily Load to maintain likelihood of meeting regulatory chlorophyll-a standards in the future that is similar to present. By understanding the effects of largely unmanageable characteristics of the bay, water quality managers can reassess efforts on limiting factors they can control relative to those they cannot.

Effect of biochar and activated carbon on production of methane and odorous volatile sulfur compounds in fed-batch anaerobic digestion of poultry slaughterhouse sludge - Navid Farahmandzad; Saravanan R. Shanmugam; Shima Rezaei; Grace Booher; Edward T. Drabold; Nitesh Kasera; Sushil Adhikari; Brendan Higgins (Journal of Environmental Chemical Engineering, 2026)

Neurobehavioral and metabolic consequences of embryonic triphenyl phosphate exposure across the lifespan in zebrafish - Andrew B. Hawkey; Perry Piatos; Zade R. Holloway; Dilanaz Unal; Jonna Boyda; Richard T. Di Giulio; Edward D. Levin (Neurotoxicology and Teratology, 2026)

Aiding Imperiled Fish and Mussel Conservation Using Swimming Performance Metrics to Inform the Design or Modification of Road Stream Crossings - Allie N. Burdette-Lapuz; Malachi R. Hubbard; Cameron M. Emadi; Preston T. Bean; Edward M. Mager (Fishes, 2026)
Culvert construction at stream crossing sites can lead to zones of high-velocity water flow which can disrupt the dispersal and connectivity of species of greatest conservation need (SGCN) in Texas. To help inform effective culvert design, the swimming performance of the following seven fish species has been measured, the first three of which are SGCN themselves, and the last four serve as hosts for glochidia of SGCN mussels (mussel genera indicated in parentheses): Colorado Roundnose Minnow, Texas Shiner, Headwater Catfish, Largemouth Bass (host for Lampsilis spp.), Green Sunfish (host for Lampsilis spp.), Channel Catfish (host for Cyclonaias spp.) and Blacktail Shiner (host for Fusconaia spp.). The primary objective was to measure the critical swimming speeds (Ucrit) under a range of relevant temperatures (15, 22.5, and 30 °C) to be used in site-specific calculations of culvert water velocities (Vf). A secondary objective was to collect additional physiological endpoints of relevance to overall swimming performance, including maximum burst swimming speed (Umax), metabolic rate measurements (i.e., standard (SMR), maximum (MMR) and aerobic scope (AS)) and calculations of cost of transport (COT) and optimal swimming speed (Uopt). As expected, Ucrit tended to increase with increasing temperature for several species with metabolic rate measurements following congruent trends, whereas Umax exhibited thermal independence for all species.

The Role of Gene Flow in the Diversification of the Monkey Treefrog Complex Across the South American Dry Diagonal - Felipe Camurugi; Vinícius A. São Pedro; Felipe Magalhães; Marcelo Gehara; Eliana F. Oliveira; Gabriel C. Costa; Frank T. Burbrink; Edward A. Myers; Guarino R. Colli; Miguel T. Rodrigues; Adrian A. Garda (Zoologica Scripta, 2026)
Understanding Neotropical megadiversity remains challenging due to fundamental taxonomic issues, including identifying and describing cryptic species and their distribution, and the limited knowledge of key factors driving biological diversification. Such challenges are especially prominent in diverse clades with high levels of cryptic species, such as many Neotropical frogs. Herein, we conduct a mitochondrial phylogenetic study on monkey treefrogs in the genus Pithecopus and a multilocus analysis of the P. hypochondrialis species group throughout its distribution in the South American dry diagonal (DD). Our goals were to infer the main lineages and identify historical factors that led to their divergence. Among nine currently recognised species, we found 14 well‐structured mitochondrial lineages in two main clades, which diversified during the Paleogene/Neogene transition. The lowland clade is widely distributed in the DD, and our multilocus analysis suggests it comprises seven geographically structured lineages: P. azureus , two lineages of P. hypochondrialis , two species and one lineage for the P. nordestinus complex, and Pithecopus sp. Considering the geomorphological history of the region, diversification may have been promoted by allopatric speciation during Miocene paleogeographic events, especially the Brazilian Plateau compartmentalization and fluctuations in the São Francisco River water volume. Furthermore, gene flow between some lineages may be explained by niche conservatism and demographic expansions during the late Pleistocene, a period marked by climatic fluctuations and biome shifts. Our results reinforce the importance of both Neogene tectonic activity and Quaternary climatic fluctuations in shaping the Neotropical biota.

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

The collective application of shorebird tracking data to conservation - Autumn‐Lynn Harrison; Candace Stenzel; Alexandra Anderson; Jessica Howell; Richard B. Lanctot; Marley Aikens; Joaquín Aldabe; Liam A. Berigan; Joël Bêty; Erik Blomberg; Juliana Bosi de Almeida; Andy J. Boyce; et al. (Conservation Biology, 2026)
Addressing urgent conservation issues, such as the drastic declines of North American migratory birds, requires creative, evidence‐based, efficient, and collaborative approaches. The abundance of over 50% of monitored North American shorebird populations has declined by over 50% since 1980. To address these declines, we developed a partnership of scientists and practitioners called the Shorebird Science and Conservation Collective (hereafter the collective ). The collective was founded to translate the combined findings of shorebird tracking data into on‐the‐ground conservation action. With advice from an advisory group, the collective acts as an intermediary whereby dedicated staff collate and analyze data contributions from scientists to support knowledge requests from conservation practitioners. In its first three years, data contributions from 75 organizations include over 7.1 million shorebird observations forming movement paths of 3420 individuals representing 36 species tracked across the Americas and have informed 18 conservation projects spanning education, land and species management, land conservation, and policy requests. Others engaged in translational science from big data could consider similar knowledge‐sharing models that prioritize usable data products, foster collaborative engagement between science experts and practitioners, build focused communities around topics or taxonomic groups, and employ a proof‐of‐concept phase to develop scalable solutions while making progress toward long‐term funding to sustain impact. As the volume of scientific data continues to grow, intermediaries, such as the collective, can be vital liaisons to rapidly integrate and interpret research to support conservation action. Dedicated to the memory of Shiloh Schulte and his conservation achievements for shorebirds.

Factors affecting 87Sr/86Sr preservation in conodont apatite: An example from the Ordovician of Baltoscandia - Christopher T. Conwell; Matthew R. Saltzman; Anders Lindskog; Mats E. Eriksson; Elizabeth M. Griffith; Stephen A. Leslie; Cole T. Edwards; Olle Hints; Achim D. Herrmann (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

A Conceptual Framework and Methods for Studying the Connectivity of Fishes - Jordanna N. Bergman; Jessica A. Robichaud; Jasper McCutcheon; Michael T. Booth; Brendan Campbell; Grace A. Casselberry; Cienna R. Cooper; Bronwyn M. Gillanders; Lucas P. Griffin; Edward Hale; Luc LaRochelle; Karen J. Murchie; et al. (Fish and Fisheries, 2026)
Connectivity is a multifaceted concept that has important implications for the management and conservation of marine and freshwater fishes. We developed a conceptual framework that encompasses multiple, interrelated categories of connectedness, including landscape (e.g., structural, functional) connectivity and ecological (e.g., trophic, genetic, demographic) connectivity, that together shape the flow of organisms, energy and information across ecosystems. We also synthesised six key methods that can be used to study connectivity of fishes: (1) telemetry, including satellite, acoustic, radio and passive integrated transponders (PIT), (2) mark‐recapture, (3) environmental tracers, including stable isotopes and otolith‐microchemistry, (4) genetics, (5) community structure analysis and (6) emerging technologies and tools (e.g., remote sensing and artificial intelligence). For each method, we describe the categories of connectivity it can assess and provide real‐world examples where they have been effectively used. We also identify limitations of each method. This article highlights the diverse and evolving toolbox of methods used to assess fish connectivity, underscoring the need for continued collaboration, innovation and integration of new approaches to refine our understanding and address remaining challenges in this critical area of aquatic ecology and fisheries management.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Record Rainfall from the Enhanced Southwest Monsoon in Metro Manila, Philippines: A Comparative Study of Recent Events - Lyndon Mark Payanay Olaguera; Alwin Andriel L. Bathan; Edward Kyle Badua; Erica N. Bañares; Clint Eldrick R. Petilla; John A. Manalo; Faye Abigail T. Cruz; Jose Ramon T. Villarin (Asia-Pacific Journal of Atmospheric Sciences, 2026)

The history of Martian water during the Hesperian and Amazonian epochs - Bruce M. Jakosky; Noora R. Alsaeed; Eryn M. Cangi; Michael S. Chaffin; Justin Deighan; Margaret E. Landis; Michael T. Mellon; Edward M.B. Thiemann (Icarus, 2026)

Microtopography and surface features of the mid-Pleistocene Kalkkop impact crater and Palaeolake, South Africa - K.L. Kirsten; A.F. Blackwood; D.L. Delaney; T.R. Edwards; F. Fourie; T. Haberzettl; K. Hadebe; J. Hellstrom; M. Huber; M. Keebine; A.M. Muasya; A.H.I. Razafimanantsoa; et al. (CATENA, 2026)

Investigating 210Pb boundary scavenging on a high-energy, river-dominated margin - Evan R. Flynn; Steven A. Kuehl; Courtney K. Harris; J. Jotautas Baronas; Edward T. Tipper (Estuarine, Coastal and Shelf Science, 2025)

Proof-of-concept for sterility induction in sablefish (Anoplopoma fimbria) via a scalable immersion-based gene silencing approach - Yuzo R. Yanagitsuru; Edward S. Hayman; William T. Fairgrieve; Yonathan Zohar; Ten-Tsao Wong; J. Adam Luckenbach (Aquaculture, 2025)

Hidden Nutrient Gaps: The Association Between Healthy Eating index-2020 Scores and Micronutrient Gaps - C. Edwards; J. Townsend; P. Sapp; T. Kirby; L. Nyman; R. Esposito (Journal of the Academy of Nutrition and Dietetics, 2025)

AG1® Supplementation Improves Gut Microbiome Composition and Relative Abundance of Growth/Nutrient Metabolism Gene Pathways in Adults with Occasional Gastrointestinal Issues - T. Kirby; J. Townsend; P. Sapp; C. Edwards; J. Wright; R. Lamendella; L. Nyman; R. Esposito (Journal of the Academy of Nutrition and Dietetics, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Tsunami hazard assessment along the US East Coast from extreme sources in the North Atlantic Ocean: a limited probabilistic analysis - Stephan T. Grilli; Lauren Schambach; Maryam Mohammadpour; Annette R. Grilli; James T. Kirby; Edward S. Fratto; Fengyan Shi (Natural Hazards, 2025)
Coastal hazard is assessed along the US East Coast (USEC) through model simulation of 14 probable maximum tsunamis (PMTs) from sources located in the North Atlantic Ocean basin, in terms of: (i) standard inundation maps and other hazard products, and (ii) a limited probabilistic tsunami hazard analysis (PTHA) based on these. Tsunami sources are based on historical records or are hypothetical, including extreme seismic events in the Puerto Rico Trench (PRT)/Caribbean Arc area and in the Açores Convergence Zone (ACZ), near-field submarine mass failures (SMF) on or near the continental shelf break, and large scale volcanic flank collapses of the Cumbre Vieja Volcano (CVV), on La Palma in the Canary Archipelago. Various state-of-the-art models are used to simulate tsunami generation from these sources and propagation to the USEC, in a series of nested grids, by one-way coupling. Based on these results, hazard metrics are computed for each PMT and their envelope as: (i) a synoptic representation along the entire USEC (with results interpolated on the 5 m isobath in coarse 450 m grids), and (ii) high-resolution (10–30 m) inundation maps, for about 30% of the USEC to date, prioritizing the most exposed areas. While existing maps can be accessed in a repository, in this paper, we focus on assessing the synoptic tsunami hazard using 4 hazard metrics (surface elevation, flow velocity, momentum force and arrival time) and their combination into a Tsunami Intensity Index ( TII ) introduced in earlier work. A comparison of metrics for each PMT shows similar alongshore patterns of higher/lower impact, due to wave focusing and defocusing effects induced by the shelf bathymetry; on this basis, 14 focusing areas are identified from Maine to southern Florida, where tsunami hazard for any PMT is always relatively larger. The limited PTHA is then performed based on the PMT metrics, using estimated return period ranges for each source (in the $$T_r\in [500; 50,000]$$ T r ∈ [ 500 ; 50 , 000 ] year interval), from the literature and/or educated guesses. This analysis yields return periods along the USEC for 5 classes of metrics and the TII . The PTHA results are then interpolated to provide the same metrics along the USEC for $$T_r = 500$$ T r = 500 and 2,500 years, which are standard in geohazard assessment. PTHA results show, depending on low-high estimates of PMT return periods that: (i) up to $$T_r = 137-261$$ T r = 137 - 261 years, there is no probable tsunami hazard; (ii) for $$T_r =500$$ T r = 500 years, tsunami hazard would be expected to be low-medium and only larger near some focusing sites, with flooding metrics at par with a severe coastal storm; and (iii) for $$T_r =2,500$$ T r = 2 , 500 years, which is commensurate with the longest return periods considered on the US west Coast for large Cascadia events, the USEC would face high tsunami hazard, with widespread destruction near the focusing areas and severe impact elsewhere. As uncertainties are large on the estimated return period ranges used and, hence, on the results of this limited PTHA, while raising awareness for the potential tsunami hazard facing the USEC, this work stresses the need for conducting a more in-depth and comprehensive PTHA, including using a larger selection of tsunami sources and further supporting and refining the range of return periods selected for each of those. Such work has been initiated and will be the object of future papers.

Rhenium-osmium and oxygen isotope homogeneity during the 2022 Mauna Loa eruption and implications for basaltic magma storage - Emily A. Rhoads; Anton Kutyrev; Ilya N. Bindeman; Kendra J. Lynn; Frank A. Trusdell; Drew T. Downs; Hunter R. Edwards; Geoffrey W. Cook; James M. D. Day (Bulletin of Volcanology, 2025)
Mauna Loa is one of the largest and most active volcanoes on Earth. The most recent eruption of Mauna Loa started on 27 November 2022, lasted for 13 days, and was preceded by the longest repose time of 38 years in its modern history. In this contribution, new trace- and highly siderophile-element (HSE: Os, Ir, Ru, Pt, Pd, Re) abundances, 187 Re- 187 Os, and 18 O/ 16 O data are reported for the 2022 lavas. These lavas have a limited range of MgO (6.2 ± 0.1 wt.%) and Ni (83 ± 2 µg/g), with a broader range of Re (0.3 to 1.3 ng/g) and consistent Os (0.031 to 0.080 ng/g) contents. They have 187 Os/ 188 Os ratios (0.1345 to 0.1385) which are, on average, more radiogenic than Mauna Loa picrites (0.1331 to 0.1349) and are similar in composition to more differentiated Mauna Loa tholeiite lavas (0.1340 to 0.1381). The oxygen isotope compositions of glassy samples are 5.35 ± 0.15‰ ( n = 13) and span a range in δ 18 O of + 5.0 to + 5.5‰, with an average composition 0.2 to 0.3‰ lower than MORB. The δD value is − 81 ± 11‰ ( n = 5) at very low (0.03 ± 0.015 wt.%) H 2 O concentrations. The 2022 Mauna Loa eruption is similar in terms of δ 18 O but contrasts in terms of 187 Os/ 188 Os variability, with the recent longer-lived eruptions on La Palma (Canary Islands; 85 days) in 2021 and on the Reykjanes Peninsula (Iceland) that began in 2021 and are still ongoing. Initial lavas were more fractionated for both the Canary Islands and Iceland eruptions, producing more radiogenic Os isotope compositions than later erupted products. The 2022 Mauna Loa eruption showed no such trends. The limited range in isotope compositions of the 2022 Mauna Loa lavas and their strongly fractioned HSE patterns reflect long-term storage, crystal fractionation, and assimilation of related basaltic volcanic edifice materials by the parent magma beneath the volcano prior to eruption triggering. Eruption of differentiated and homogeneous tholeiite lavas at the summit caldera and high on the volcano’s flank, with emplacement of accumulative picrites lower on the volcano, are consistent with neutral buoyancy arguments.

Burn parameters affect PAH emissions at conditions relevant for prescribed fires - Karl Töpperwien; Guillaume Vignat; Alexandra J. Feinberg; Conner Daube; Mitchell W. Alton; Edward C. Fortner; Manjula R. Canagaratna; Matthias F. Kling; Mary Johnson; Kari Nadeau; Scott Herndon; John T. Jayne; et al. (Atmospheric Pollution Research, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Correction: Sequence Divergence in Venom Genes Within and Between Montane Pitviper (Viperidae: Crotalinae: Cerrophidion) Species is Driven by Mutation–Drift Equilibrium - Ramses Alejandro Rosales‑Garcia; Rhett M. Rautsaw; Erich P. Hofmann; Christoph I. Grünwald; Hector Franz‑Chavez; Ivan T. Ahumada‑Carrillo; Ricardo Ramirez‑Chaparro; Miguel Angel de la Torre‑Loranca; Jason L. Strickland; Andrew J. Mason; Matthew L. Holding; Miguel Borja; et al. (Journal of Molecular Evolution, 2025)

Routine large-scale movements of the yelloweye rockfish (Sebastes ruberrimus) - Leif K. Rasmuson; Matthew T. O. Blume; Kelly A. Lawrence; Bruce M. Laughlin; Christopher A. Edwards; Mark R. Terwilliger; A. Camille Ayrea; Alexandra G. McInturf; Bryan J. Legare; Taylor K. Chapple (Frontiers in Marine Science, 2025)
Of the seven species of Pacific rockfish declared overfished in the California Current in 2008, yelloweye rockfish ( Sebastes ruberrimus ) is the only remaining overfished rockfish species. Part of the original rebuilding plan included designation of a yelloweye rockfish conservation area, a rocky reef closed off the Central Coast of Oregon that is closed to bottom fishing. The yelloweye rockfish conservation area’s ability to help rebuild the population, is predicated on the theory that demersal rockfishes are relatively sedentary. However, in the years since being declared overfished, acoustic tagging studies suggested yelloweye rockfish did not remain in the yelloweye rockfish conservation area. However, where they went remained a mystery. In this paper we describe the use of pop-off satellite tags to conduct a mark-recapture study of 11 yelloweye rockfish tagged within the Stonewall Bank Yelloweye Rockfish Conservation Area. We used back-in-time particle tracking coupled with an ocean circulation model in an attempt to increase the precision in the location at which each tag shed off the fish, and further validated that location by associating it to the underlying seafloor habitat type. Ten out of eleven tags were shed from the fish while it was outside the Stonewall Bank Yelloweye Rockfish Conservation Area’s boundary. While most fish remained within 50 km of the Stonewall Bank Yelloweye Rockfish Conservation Area, one tagged fish swam to an offshore reef off Central Washington (~40 km from the shore). Backtracked locations were more likely over rock than the initial satellite transmission, indicating the method was effective at identifying tag shed locations. We found no relationship between days at large, fish sex or length and the distance between release site and shed location. Our work supports a growing body of work that suggests yelloweye rockfish have less site fidelity than previously hypothesized.

Light buckets and laser beams: mechanisms and applications of photobiomodulation (PBM) therapy - David W. Frankowski; Luigi Ferrucci; Praveen R. Arany; Dawn Bowers; Janis T. Eells; Francisco Gonzalez-Lima; Nicole L. Lohr; Brendan J. Quirk; Harry T. Whelan; Edward G. Lakatta (GeroScience, 2025)
Photobiomodulation (PBM) therapy, a non-thermal light therapy using nonionizing light sources, has shown therapeutic potential across diverse biological processes, including aging and age-associated diseases. In 2023, scientists from the National Institute on Aging (NIA) Intramural and Extramural programs convened a workshop on the topic of PBM to discuss various proposed mechanisms of PBM action, including the stimulation of mitochondrial cytochrome C oxidase, modulation of cell membrane transporters and receptors, and the activation of transforming growth factor-β1. They also reviewed potential therapeutic applications of PBM across a range of conditions, including cardiovascular disease, retinal disease, Parkinson’s disease, and cognitive impairment. Workshop participants largely agreed that PBM holds immense potential as a safe and effective therapeutic approach for a wide range of age-related diseases and cognitive decline. While further research is needed to fully elucidate its mechanisms and optimize treatment protocols, the findings presented at the NIA workshop provide strong evidence for the continued investigation and clinical translation of this promising, inexpensive, safe technology, to aging and age-associated diseases. Here, we review the research presented and discussion held at the meeting. In addition, the text has been updated, where applicable, with recent research findings that have been made since the meeting occurred.

Controls on spatial variation in porewater methane concentrations across United States tidal wetlands - Erika L. Koontz; Sarah M. Parker; Alice E. Stearns; Brian J. Roberts; Caitlin M. Young; Lisamarie Windham-Myers; Patricia Y. Oikawa; J. Patrick Megonigal; Genevieve L. Noyce; Edward J. Buskey; R. Kyle Derby; Robert P. Dunn; et al. (Science of The Total Environment, 2024)

Deployment-invariant probability of detection characterization for aerial LiDAR methane detection - Michael J. Thorpe; Aaron Kreitinger; Dominic T. Altamura; Cameron D. Dudiak; Bradley M. Conrad; David R. Tyner; Matthew R. Johnson; Jason K. Brasseur; Peter A. Roos; William M. Kunkel; Asa Carre-Burritt; Jerry Abate; et al. (Remote Sensing of Environment, 2024)

Middle Ordovician paleoenvironmental evolution of the western Laurentian carbonate platform: Evidence for persistent oxygenation of the shallow ocean and implications for biodiversification - Charles W. Diamond; Matthew R. Saltzman; Timothy W. Lyons; Cole T. Edwards (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Lithium isotope stratigraphy and Ordovician weathering - Y. Datu Adiatma; Matthew R. Saltzman; Xiao-Ming Liu; Xi-Kai Wang; Cole T. Edwards (Earth and Planetary Science Letters, 2024)

A Transcriptomic Comparative Study of Cranial Vasculature - Jianing Zhang; Jee-Yeon Ryu; Selena-Rae Tirado; Lawrence D. Dickinson; Aviva Abosch; M. Ali Aziz-Sultan; Alan S. Boulos; Daniel L. Barrow; H. Hunt Batjer; Tamar R. Binyamin; Spiros L. Blackburn; Edward F. Chang; et al. (Translational Stroke Research, 2024)

High resolution luminescence and radiocarbon dating of Holocene Aeolian silt (loess) in west Greenland - D. Sechi; T. Stevens; P. Hällberg; R.H. Smittenberg; M. Molnár; G.T. Kertész; J.P. Buylaert; R. Schneider; C. Edward; Keld Romer Rasmussen; Niels Aage Tvis Knudsen; S. Andreucci; et al. (Quaternary Geochronology, 2024)

A 561-yr (1461-2022 CE) summer temperature reconstruction for Mid-Atlantic-Northeast USA shows connections to volcanic forcing and atmospheric circulation - Grant L. Harley; Justin T. Maxwell; Karen E. King; Shelly A. Rayback; Edward R. Cook; Christopher Hansen; R. Stockton Maxwell; Frederick Reinig; Jan Esper; Tsun Fung Au; Ellen V. Bergan; Katherine E. Brings; et al. (Climatic Change, 2024)
Contextualizing current increases in Northern Hemisphere temperatures is precluded by the short instrumental record of the past ca. 120 years and the dearth of temperature-sensitive proxy records, particularly at lower latitudes south of <50 °N. We develop a network of 29 blue intensity chronologies derived from tree rings of Tsuga canadensis (L.) Carrière and Picea rubens Sarg. trees distributed across the Mid-Atlantic and Northeast USA (MANE)—a region underrepresented by multi-centennial temperature records. We use this network to reconstruct mean March-September air temperatures back to 1461 CE based on a model that explains 62% of the instrumental temperature variance from 1901−1976 CE. Since 1998 CE, MANE summer temperatures are consistently the warmest within the context of the past 561 years exceeding the 1951−1980 mean of +1.3 °C. Cool summers across MANE were frequently volcanically forced, with significant ( p <0.05) temperature departures associated with 80% of the largest tropical ( n =13) and extratropical ( n =15) eruptions since 1461 CE. Yet, we find that more of the identified cool events in the record were likely unforced by volcanism and either related to stochastic variability or atmospheric circulation via significant associations ( p <0.05) to regional, coastal sea-surface temperatures, 500-hpa geopotential height, and 300-hpa meridional and zonal wind vectors. Expanding the MANE network to the west and south and combining it with existing temperature-sensitive proxies across North America is an important next step toward producing a gridded temperature reconstruction field for North America.

Wind dispersed tree species have greater maximum height - Ferry Slik; Bruno X. Pinho; Daniel M. Griffith; Edward Webb; Akhilesh Singh Raghubanshi; Adriano C. Quaresma; Aida Cuni Sanchez; Aisha Sultana; Alexandre F. Souza; Andreas Ensslin; Andreas Hemp; Andrew Lowe; et al. (Global Ecology and Biogeography, 2024)
Aim We test the hypothesis that wind dispersal is more common among emergent tree species given that being tall increases the likelihood of effective seed dispersal. Location Americas, Africa and the Asia‐Pacific. Time period 1970–2020. Major taxa studied Gymnosperms and Angiosperms. Methods We used a dataset consisting of tree inventories from 2821 plots across three biogeographic regions (Americas, Africa and Asia‐Pacific), including dry and wet forests, to determine the maximum height and dispersal strategy of 5314 tree species. A web search was used to determine whether species were wind‐dispersed. We compared differences in tree species maximum height between biogeographic regions and examined the relationship between species maximum height and wind dispersal using logistic regression. We also tested whether emergent tree species, that is species with at least one individual taller than the 95% height percentile in one or more plots, were disproportionally wind‐dispersed in dry and wet forests within each biogeographic region. Results Our dataset provides maximum height values for 5314 tree species, of which more than half (2914) had no record of this trait in existing global databases. We found that, on average, tree species in the Americas have lower maximum heights compared to those in Africa and the Asia Pacific. The probability of wind dispersal increased significantly with tree species maximum height and was significantly higher among emergent than non‐emergent tree species in both dry and wet forests in all three biogeographic regions. Main conclusion Wind dispersal is more prevalent in tall, emergent tree species than in non‐emergent species and may thus be an important factor in the evolution of tree species maximum height. By providing the most comprehensive dataset so far of tree species maximum height and wind dispersal strategies, this study paves the way for advancing our understanding of the eco‐evolutionary drivers of tree size.

Pyrrhotites in asteroid 162173 Ryugu: Records of the initial changes on their surfaces with aqueous alteration - Hiroharu Yui; Shu-hei Urashima; Morihiko Onose; Mayu Morita; Shintaro Komatani; Izumi Nakai; Yoshinari Abe; Yasuko Terada; Hisashi Homma; Kazuko Motomura; Kiyohiro Ichida; Tetsuya Yokoyama; et al. (Geochimica et Cosmochimica Acta, 2024)

Deliberately introduced dung beetles in A ustralia: 12 years of occurrence and abundance records from 2001 to 2022 - Jacob D. Berson; Penelope B. Edwards; T. James Ridsdill‐Smith; Christopher K. Taylor; Daniel J. Anderson; Nigel R. Andrew; Russell A. Barrow; David A. Cousins; Robert N. Emery; Laura L. Fagan; Rhiannon M. Foster; Lucas G. Harwood; et al. (Ecology, 2024)
Since 1968, the Australian Dung Beetle Project has carried out field releases of 43 deliberately introduced dung beetle species for the biological control of livestock dung and dung‐breeding pests. Of these, 23 species are known to have become established. For most of these species, sufficient time has elapsed for population expansion to fill the extent of their potential geographic range through both natural and human‐assisted dispersal. Consequently, over the last 20 years, extensive efforts have been made to quantify the current distribution of these introduced dung beetles, as well as the seasonal and spatial variation in their activity levels. Much of these data and their associated metadata have remained unpublished, and they have not previously been synthesized into a cohesive dataset. Here, we collate and report data from the three largest dung beetle monitoring projects from 2001 to 2022. Together, these projects encompass data collected from across Australia, and include records for all 23 species of established dung beetles introduced for biocontrol purposes. In total, these data include 22,718 presence records and 213,538 absence records collected during 10,272 sampling events at 546 locations. Most presence records (97%) include abundance data. In total, 1,752,807 dung beetles were identified as part of these data. The distributional occurrence and abundance data can be used to explore questions such as factors influencing dung beetle species distributions, dung beetle biocontrol, and insect‐mediated ecosystem services. These data are provided under a CC‐BY‐NC 4.0 license and users are encouraged to cite this data paper when using the data.

Structural insights and cytotoxicity evaluation of benz[e]indole pyrazolyl-substituted amides - Abdul Qaiyum Ramle; Nadia Nabihah Mohd Yusof Chan; Min Phin Ng; Chun Hoe Tan; Kae Shin Sim; Edward R. T. Tiekink; Chee Chin Fei (Molecular Diversity, 2024)

Changes in Global Warming’s Six Americas: an analysis of repeat respondents - Megan Ayers; Jennifer R. Marlon; Matthew T. Ballew; Edward W. Maibach; Seth A. Rosenthal; Connie Roser-Renouf; Anthony Leiserowitz (Climatic Change, 2024)

Speculations on the Paleozoic legacy of Gondwana amalgamation - J. Brendan Murphy; R. Damian Nance; Stephen T. Johnston; Josep M. Casas; Peter A. Cawood; Edward J. Matheson; Peir K. Pufahl; Wei Dan; J. Javier Álvaro; Philip J. Heron; Rob A. Strachan (Gondwana Research, 2024)

Pervasive aqueous alteration in the early Solar System revealed by potassium isotopic variations in Ryugu samples and carbonaceous chondrites - Yan Hu; Frédéric Moynier; Wei Dai; Marine Paquet; Tetsuya Yokoyama; Yoshinari Abe; Jérôme Aléon; Conel M. O'D. Alexander; Sachiko Amari; Yuri Amelin; Ken-ichi Bajo; Martin Bizzarro; et al. (Icarus, 2024)

Closing the gap between existing large‐area imaging research and marine conservation needs - Orion S. McCarthy; Kanisha Contractor; Will F. Figueira; Arthur C. R. Gleason; T. Shay Viehman; Clinton B. Edwards; Stuart A. Sandin (Conservation Biology, 2024)
Emerging technology has immense potential to increase the scale and efficiency of marine conservation. One such technology is large‐area imaging (LAI), which relies on structure‐from‐motion photogrammetry to create composite products, including 3‐dimensional (3‐D) environmental models, that are larger in spatial extent than the individual images used to create them. Use of LAI has become widespread in certain fields of marine science, primarily to measure the 3D structure of benthic ecosystems and track change over time. However, the use of LAI in the field of marine conservation appears limited. We conducted a review of the coral reef literature on the use of LAI to identify research themes and regional trends in applications of this technology. We also surveyed 135 coral reef scientists and conservation practitioners to determine community familiarity with LAI, evaluate barriers practitioners face in using LAI, and identify applications of LAI believed to be most exciting or relevant to coral conservation. Adoption of LAI was limited primarily to researchers at institutions based in advanced economies and was applied infrequently to conservation, although conservation practitioners and survey respondents from emerging economies indicated they expect to use LAI in the future. Our results revealed disconnect between current LAI research topics and conservation priorities identified by practitioners, highlighting the need for more diverse, conservation‐relevant research using LAI. We provide recommendations for how early adopters of LAI (typically Global North scientists from well‐resourced institutions) can facilitate access to this conservation technology. These recommendations include developing training resources, creating partnerships for data storage and analysis, publishing standard operating procedures for LAI workflows, standardizing methods, developing tools for efficient data extraction from LAI products, and conducting conservation‐relevant research using LAI.

Fine-mapping of a major locus for Fusarium wilt resistance in flax (Linum usitatissimum L.) - S. Cloutier; T. Edwards; C. Zheng; H. M. Booker; T. Islam; K. Nabetani; H. R. Kutcher; O. Molina; F. M. You (Theoretical and Applied Genetics, 2024)
Key message Fine-mapping of a locus on chromosome 1 of flax identified an S-lectin receptor-like kinase (SRLK) as the most likely candidate for a major Fusarium wilt resistance gene. Abstract Fusarium wilt, caused by the soil-borne fungal pathogen Fusarium oxysporum f. sp. lini , is a devastating disease in flax. Genetic resistance can counteract this disease and limit its spread. To map major genes for Fusarium wilt resistance, a recombinant inbred line population of more than 700 individuals derived from a cross between resistant cultivar ‘Bison’ and susceptible cultivar ‘Novelty’ was phenotyped in Fusarium wilt nurseries at two sites for two and three years, respectively. The population was genotyped with 4487 single nucleotide polymorphism (SNP) markers. Twenty-four QTLs were identified with IciMapping, 18 quantitative trait nucleotides with 3VmrMLM and 108 linkage disequilibrium blocks with RTM-GWAS. All models identified a major QTL on chromosome 1 that explained 20–48% of the genetic variance for Fusarium wilt resistance. The locus was estimated to span ~ 867 Kb but included a ~ 400 Kb unresolved region. Whole-genome sequencing of ‘CDC Bethune’, ‘Bison’ and ‘Novelty’ produced ~ 450 Kb continuous sequences of the locus. Annotation revealed 110 genes, of which six were considered candidate genes. Fine-mapping with 12 SNPs and 15 Kompetitive allele-specific PCR (KASP) markers narrowed down the interval to ~ 69 Kb, which comprised the candidate genes Lus10025882 and Lus10025891 . The latter, a G-type S-lectin receptor-like kinase (SRLK) is the most likely resistance gene because it is the only polymorphic one. In addition, Fusarium wilt resistance genes previously isolated in tomato and Arabidopsis belonged to the SRLK class. The robust KASP markers can be used in marker-assisted breeding to select for this major Fusarium wilt resistance locus.

Diverse pathways for climate resilience in marine fishery systems - Jacob G. Eurich; Whitney R. Friedman; Kristin M. Kleisner; Lily Z. Zhao; Christopher M. Free; Meghan Fletcher; Julia G. Mason; Kanae Tokunaga; Alba Aguion; Andrea Dell'Apa; Mark Dickey‐Collas; Rod Fujita; et al. (Fish and Fisheries, 2024)
Both the ecological and social dimensions of fisheries are being affected by climate change. As a result, policymakers, managers, scientists and fishing communities are seeking guidance on how to holistically build resilience to climate change. Numerous studies have highlighted key attributes of resilience in fisheries, yet concrete examples that explicitly link these attributes to social‐ecological outcomes are lacking. To better understand climate resilience, we assembled 18 case studies spanning ecological, socio‐economic, governance and geographic contexts. Using a novel framework for evaluating 38 resilience attributes, the case studies were systematically assessed to understand how attributes enable or inhibit resilience to a given climate stressor. We found population abundance, learning capacity, and responsive governance were the most important attributes for conferring resilience, with ecosystem connectivity, place attachment, and accountable governance scoring the strongest across the climate‐resilient fisheries. We used these responses to develop an attribute typology that describes robust sources of resilience, actionable priority attributes and attributes that are case specific or require research. We identified five fishery archetypes to guide stakeholders as they set long‐term goals and prioritize actions to improve resilience. Lastly, we found evidence for two pathways to resilience: (1) building ecological assets and strengthening communities, which we observed in rural and small‐scale fisheries, and (2) building economic assets and improving effective governance, which was demonstrated in urban and wealthy fisheries. Our synthesis presents a novel framework that can be directly applied to identify approaches, pathways and actionable levers for improving climate resilience in fishery systems.

Sedimentological and geochemical characterization of a varved sediment record from the northern Neotropics - Edward Duarte; Jonathan Obrist-Farner; Susan R. H. Zimmerman; Erik T. Brown; Robert Brown (Journal of Paleolimnology, 2023)

Sequence Divergence in Venom Genes Within and Between Montane Pitviper (Viperidae: Crotalinae: Cerrophidion) Species is Driven by Mutation–Drift Equilibrium - Ramses Alejandro Rosales-García; Rhett M. Rautsaw; Erich P. Hofmann; Christoph I. Grünwald; Hector Franz-Chavez; Ivan T. Ahumada-Carrillo; Ricardo Ramirez-Chaparro; Miguel Angel de la Torre-Loranca; Jason L. Strickland; Andrew J. Mason; Matthew L. Holding; Miguel Borja; et al. (Journal of Molecular Evolution, 2023)

Retaining natural vegetation to safeguard biodiversity and humanity - Jeremy S. Simmonds; Andres Felipe Suarez‐Castro; April E. Reside; James E. M. Watson; James R. Allan; Scott C. Atkinson; Pasquale Borrelli; Nigel Dudley; Stephen Edwards; Richard A. Fuller; Edward T. Game; Simon Linke; et al. (Conservation Biology, 2023)
Global efforts to deliver internationally agreed goals to reduce carbon emissions, halt biodiversity loss, and retain essential ecosystem services have been poorly integrated. These goals rely in part on preserving natural (e.g., native, largely unmodified) and seminatural (e.g., low intensity or sustainable human use) forests, woodlands, and grasslands. To show how to unify these goals, we empirically derived spatially explicit, quantitative, area‐based targets for the retention of natural and seminatural (e.g., native) terrestrial vegetation worldwide. We used a 250‐m‐resolution map of natural and seminatural vegetation cover and, from this, selected areas identified under different international agreements as being important for achieving global biodiversity, carbon, soil, and water targets. At least 67 million km 2 of Earth's terrestrial vegetation (∼79% of the area of vegetation remaining) required retention to contribute to biodiversity, climate, soil, and freshwater conservation objectives under 4 United Nations’ resolutions. This equates to retaining natural and seminatural vegetation across at least 50% of the total terrestrial (excluding Antarctica) surface of Earth. Retention efforts could contribute to multiple goals simultaneously, especially where natural and seminatural vegetation can be managed to achieve cobenefits for biodiversity, carbon storage, and ecosystem service provision. Such management can and should co‐occur and be driven by people who live in and rely on places where natural and sustainably managed vegetation remains in situ and must be complemented by restoration and appropriate management of more human‐modified environments if global goals are to be realized.

Updated guidelines for gene nomenclature in wheat - S. A. Boden; R. A. McIntosh; C. Uauy; S. G. Krattinger; J. Dubcovsky; W. J. Rogers; X. C. Xia; E. D. Badaeva; A. R. Bentley; G. Brown-Guedira; M. Caccamo; L. Cattivelli; et al. (Theoretical and Applied Genetics, 2023)
Key message Here, we provide an updated set of guidelines for naming genes in wheat that has been endorsed by the wheat research community. Abstract The last decade has seen a proliferation in genomic resources for wheat, including reference- and pan-genome assemblies with gene annotations, which provide new opportunities to detect, characterise, and describe genes that influence traits of interest. The expansion of genetic information has supported growth of the wheat research community and catalysed strong interest in the genes that control agronomically important traits, such as yield, pathogen resistance, grain quality, and abiotic stress tolerance. To accommodate these developments, we present an updated set of guidelines for gene nomenclature in wheat. These guidelines can be used to describe loci identified based on morphological or phenotypic features or to name genes based on sequence information, such as similarity to genes characterised in other species or the biochemical properties of the encoded protein. The updated guidelines provide a flexible system that is not overly prescriptive but provides structure and a common framework for naming genes in wheat, which may be extended to related cereal species. We propose these guidelines be used henceforth by the wheat research community to facilitate integration of data from independent studies and allow broader and more efficient use of text and data mining approaches, which will ultimately help further accelerate wheat research and breeding.

Evaluation of a long-term information tool reveals continued suitability for identifying bycatch hotspots but little effect on fisher location choice - Zachary A. Siders; Robert N.M. Ahrens; Summer Martin; Edward V. Camp; Alexander R. Gaos; John H. Wang; Jamie Marchetti; T. Todd Jones (Biological Conservation, 2023)

Vulnerability to climate change of managed stocks in the California Current large marine ecosystem - Michelle M. McClure; Melissa A. Haltuch; Ellen Willis-Norton; David D. Huff; Elliott L. Hazen; Lisa G. Crozier; Michael G. Jacox; Mark W. Nelson; Kelly S. Andrews; Lewis A.K. Barnett; Aaron M. Berger; Sabrina Beyer; et al. (Frontiers in Marine Science, 2023)
Introduction Understanding how abundance, productivity and distribution of individual species may respond to climate change is a critical first step towards anticipating alterations in marine ecosystem structure and function, as well as developing strategies to adapt to the full range of potential changes. Methods This study applies the NOAA (National Oceanic and Atmospheric Administration) Fisheries Climate Vulnerability Assessment method to 64 federally-managed species in the California Current Large Marine Ecosystem to assess their vulnerability to climate change, where vulnerability is a function of a species’ exposure to environmental change and its biological sensitivity to a set of environmental conditions, which includes components of its resiliency and adaptive capacity to respond to these new conditions. Results Overall, two-thirds of the species were judged to have Moderate or greater vulnerability to climate change, and only one species was anticipated to have a positive response. Species classified as Highly or Very Highly vulnerable share one or more characteristics including: 1) having complex life histories that utilize a wide range of freshwater and marine habitats; 2) having habitat specialization, particularly for areas that are likely to experience increased hypoxia; 3) having long lifespans and low population growth rates; and/or 4) being of high commercial value combined with impacts from non-climate stressors such as anthropogenic habitat degradation. Species with Low or Moderate vulnerability are either habitat generalists, occupy deep-water habitats or are highly mobile and likely to shift their ranges. Discussion As climate-related changes intensify, this work provides key information for both scientists and managers as they address the long-term sustainability of fisheries in the region. This information can inform near-term advice for prioritizing species-level data collection and research on climate impacts, help managers to determine when and where a precautionary approach might be warranted, in harvest or other management decisions, and help identify habitats or life history stages that might be especially effective to protect or restore.

State of the California Current Ecosystem in 2021: Winter is coming? - Andrew R. Thompson; Eric P. Bjorkstedt; Steven J. Bograd; Jennifer L. Fisher; Elliott L. Hazen; Andrew Leising; Jarrod A. Santora; Erin V. Satterthwaite; William J. Sydeman; Michaela Alksne; Toby D. Auth; Simone Baumann-Pickering; et al. (Frontiers in Marine Science, 2022)
In late 2020, models predicted that a strong La Niña would take place for the first time since 2013, and we assessed whether physical and biological indicators in 2021 were similar to past La Niñas in the California Current Ecosystem (CCE). The Pacific Decadal Oscillation and Oceanic Niño Index indeed remained negative throughout 2021; the North Pacific Gyre Oscillation Index, however, remained strongly negative. The seventh largest marine heatwave on record was unexpectedly present from April to the end of 2021; however, similar to past La Niñas, this mass of warm water mostly remained seaward of the continental shelf. As expected from past La Niñas, upwelling and chlorophyll were mostly high and sea surface temperature was low throughout the CCE; however, values were close to average south of Point Conception. Similar to past La Niñas, abundances of lipid-rich, northern copepods off Oregon increased. In northern California, unlike past La Niñas, the body size of North Pacific krill ( Euphausia pacifica ) was close to average. Predictably, overall krill abundance was above average in far northern California but, unexpectedly, below average south of Cape Mendocino. Off Oregon, similar to past La Niñas, larval abundances of three of six coastal species rose, while five of six southern/offshore taxa decreased in 2021. Off California, as expected based on 2020, Northern Anchovy ( Engraulis mordax ) were very abundant, while Pacific Sardine ( Sardinops sagax ) were low. Similar to past La Niñas, market squid ( Doryteuthis opalescens ) and young of the year (YOY) Pacific Hake ( Merluccius pacificus ), YOY sanddabs ( Citharichthys spp.), and YOY rockfishes ( Sebastes spp.) increased. Southern mesopelagic (e.g., Panama lightfish Vinciguerria lucetia , Mexican lampfish Triphoturus mexicanus ) larvae decreased as expected but were still well above average, while northern mesopelagic (e.g., northern lampfish Stenobrachius leucopsarus ) larvae increased but were still below average. In line with predictions, most monitored bird species had above-average reproduction in Oregon and California. California sea lion ( Zalophus californianus ) pup count, growth, and weight were high given the abundant Anchovy forage. The CCE entered an enduring La Niña in 2021, and assessing the responses of various ecosystem components helped articulate aspects of the system that are well understood and those that need further study.

Changing minds about global warming: vicarious experience predicts self-reported opinion change in the USA - Matthew T. Ballew; Jennifer R. Marlon; Matthew H. Goldberg; Edward W. Maibach; Seth A. Rosenthal; Emily Aiken; Anthony Leiserowitz (Climatic Change, 2022)

A melting cryosphere constrains fish growth by synchronizing the seasonal phenology of river food webs - J. Ryan Bellmore; Jason B. Fellman; Eran Hood; Matthew R. Dunkle; Richard T. Edwards (Global Change Biology, 2022)
Mountain watersheds often contain a mosaic of glacier‐, snow‐, and rain‐fed streams that have distinct hydrologic, temperature, and biogeochemical regimes. However, as glaciers diminish and precipitation shifts from snow to rain, the physical and chemical characteristics that make glacial or snowmelt streams distinct from rain‐fed streams will fade. Among the unforeseen consequences of this hydrologic homogenization could be the loss of unique food webs that sustain aquatic consumers. To explore the impacts of a melting cryosphere on stream food webs, we parameterized an aquatic food web model with empirical physicochemical data from glacier‐, snow‐, and rain‐fed streams in southeast Alaska and used the model to simulate the seasonal biomass dynamics of aquatic primary producers and consumers and the growth of juvenile salmon. Model results suggest that glacier‐, snow‐, and rain‐fed streams exhibit seasonal asynchronies in the timing of biofilm and aquatic invertebrate abundance. Although warmer rain‐fed streams were more productive during the summer (June through September), colder glacial and snowmelt streams provided enhanced foraging and growth opportunities throughout the remainder of the year. For juvenile salmon that can track peaks in resource abundance within river networks, the loss of meltwater streams strongly constrained modeled growth opportunities by removing spatially and temporally distinct foraging habitats within a watershed. These findings suggest that climate change induced homogenization of high latitude river networks may result in the loss of unique food web dynamics, which could diminish the capacity of watersheds to sustain mobile consumers.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Wildfire, Smoke Exposure, Human Health, and Environmental Justice Need to be Integrated into Forest Restoration and Management - Savannah M. D’Evelyn; Jihoon Jung; Ernesto Alvarado; Jill Baumgartner; Pete Caligiuri; R. Keala Hagmann; Sarah B. Henderson; Paul F. Hessburg; Sean Hopkins; Edward J. Kasner; Meg A. Krawchuk; Jennifer E. Krenz; et al. (Current Environmental Health Reports, 2022)
Purpose of Review Increasing wildfire size and severity across the western United States has created an environmental and social crisis that must be approached from a transdisciplinary perspective. Climate change and more than a century of fire exclusion and wildfire suppression have led to contemporary wildfires with more severe environmental impacts and human smoke exposure. Wildfires increase smoke exposure for broad swaths of the US population, though outdoor workers and socially disadvantaged groups with limited adaptive capacity can be disproportionally exposed. Exposure to wildfire smoke is associated with a range of health impacts in children and adults, including exacerbation of existing respiratory diseases such as asthma and chronic obstructive pulmonary disease, worse birth outcomes, and cardiovascular events. Seasonally dry forests in Washington, Oregon, and California can benefit from ecological restoration as a way to adapt forests to climate change and reduce smoke impacts on affected communities. Recent Findings Each wildfire season, large smoke events, and their adverse impacts on human health receive considerable attention from both the public and policymakers. The severity of recent wildfire seasons has state and federal governments outlining budgets and prioritizing policies to combat the worsening crisis. This surging attention provides an opportunity to outline the actions needed now to advance research and practice on conservation, economic, environmental justice, and public health interests, as well as the trade-offs that must be considered. Summary Scientists, planners, foresters and fire managers, fire safety, air quality, and public health practitioners must collaboratively work together. This article is the result of a series of transdisciplinary conversations to find common ground and subsequently provide a holistic view of how forest and fire management intersect with human health through the impacts of smoke and articulate the need for an integrated approach to both planning and practice.

Estimated life-history traits and movements of the Caribbean reef shark (Carcharhinus perezi) in The Bahamas based on tag-recapture data - Brendan S. Talwar; Darcy Bradley; Christopher Berry; Mark E. Bond; Ian A. Bouyoucos; Annabelle M. L. Brooks; Candace Y. A. Fields; Austin J. Gallagher; Tristan L. Guttridge; Annie E. Guttridge; Neil Hammerschlag; Ian Hamilton; et al. (Marine Biology, 2022)

Attributes of climate resilience in fisheries: From theory to practice - Julia G. Mason; Jacob G. Eurich; Jacqueline D. Lau; Willow Battista; Christopher M. Free; Katherine E. Mills; Kanae Tokunaga; Lily Z. Zhao; Mark Dickey‐Collas; Mireia Valle; Gretta T. Pecl; Joshua E. Cinner; et al. (Fish and Fisheries, 2022)
In a changing climate, there is an imperative to build coupled social‐ecological systems—including fisheries—that can withstand or adapt to climate stressors. Although resilience theory identifies system attributes that supposedly confer resilience, these attributes have rarely been clearly defined, mechanistically explained, nor tested and applied to inform fisheries governance. Here, we develop and apply a comprehensive resilience framework to examine fishery systems across (a) ecological, (b) socio‐economic and (c) governance dimensions using five resilience domains: assets, flexibility, organization, learning and agency. We distil and define 38 attributes that confer climate resilience from a coupled literature‐ and expert‐driven approach, describe how they apply to fisheries and provide illustrative examples of resilience attributes in action. Our synthesis highlights that the directionality and mechanism of these attributes depend on the specific context, capacities, and scale of the focal fishery system and associated stressors, and we find evidence of interdependencies among attributes. Overall, however, we find few studies that test resilience attributes in fisheries across all parts of the system, with most examples focussing on the ecological dimension. As such, meaningful quantification of the attributes’ contributions to resilience remains a challenge. Our synthesis and holistic framework represent a starting point for critical application of resilience concepts to fisheries social‐ecological systems.

Resolving taxonomic confusion: establishing the genus Phytobacter on the list of clinically relevant Enterobacteriaceae - Theo H. M. Smits; Lavinia N. V. S. Arend; Sofia Cardew; Erika Tång-Hallbäck; Marcelo T. Mira; Edward R. B. Moore; Jorge L. M. Sampaio; Fabio Rezzonico; Marcelo Pillonetto (European Journal of Clinical Microbiology & Infectious Diseases, 2022)
Although many clinically significant strains belonging to the family Enterobacteriaceae fall into a restricted number of genera and species, there is still a substantial number of isolates that elude this classification and for which proper identification remains challenging. With the current improvements in the field of genomics, it is not only possible to generate high-quality data to accurately identify individual nosocomial isolates at the species level and understand their pathogenic potential but also to analyse retrospectively the genome sequence databases to identify past recurrences of a specific organism, particularly those originally published under an incorrect or outdated taxonomy. We propose a general use of this approach to classify further clinically relevant taxa, i.e., Phytobacter spp., that have so far gone unrecognised due to unsatisfactory identification procedures in clinical diagnostics. Here, we present a genomics and literature-based approach to establish the importance of the genus Phytobacter as a clinically relevant member of the Enterobacteriaceae family.

Litter decomposition and infiltration capacities in soils of different tropical urban land covers - Tze Kwan Fung; Daniel R. Richards; Rachel A. T. Leong; Subhadip Ghosh; Christabel W. J. Tan; Zuzana Drillet; Kit Ling Leong; Peter J. Edwards (Urban Ecosystems, 2022)

A National-Level Assessment of Lemur Hunting Pressure in Madagascar - Cortni Borgerson; Steig E. Johnson; Emma Hall; Kerry A. Brown; Pamela R. Narváez-Torres; Be Jean Rodolph Rasolofoniaina; Be Noel Razafindrapaoly; Samuel D. Merson; Katharine E. T. Thompson; Sheila M. Holmes; Edward E. Louis; Christopher D. Golden (International Journal of Primatology, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Developing a Water Quality Assessment Framework for Southwest Florida Tidal Creeks - Michael R. Wessel; Jay R. Leverone; Marcus W. Beck; Edward T. Sherwood; Jennifer Hecker; Steven West; Anthony Janicki (Estuaries and Coasts, 2022)
The three contiguous National Estuary Programs of southwest Florida, along with partners from six coastal counties, have developed a tidal creek water quality assessment framework to help prioritize natural resource investigations across a large population of tidal creeks between Tampa Bay and Estero Bay, Florida. The assessment framework is based on outcomes of a multidisciplinary study and includes a nutrient based report card that characterizes nutrient conditions relative to regional numeric nutrient criteria developed for contributing freshwater streams, identification of site-specific water quality indicators of tidal creek condition, and an online open science dashboard to display the assessment framework and provide access to all information relevant to its implementation. Application of the assessment framework has provided an actionable list of southwest Florida tidal creeks prioritized for further research and potential management action along with a host of site-specific indicator results that provide insights into drivers of tidal creek condition. The open science dashboard provides a platform for dissemination of this information in a readily accessible and reproducible format and a means to incorporate new data and indicators as they become available. Local resource managers are in need of tools to help prioritize natural resource investigations and management actions that achieve the greatest resource benefit with limited available resources. This assessment framework informs these efforts and builds capacity for future research to identify and refine management tools for these creeks where management resources, data, and sentinel biological response endpoints are limited.

Passive-Sampler-Based Bioavailability Assessment of PCB Congeners Associated with Aroclor-Containing Paint Chips in the Presence of Sediment - Guilherme R. Lotufo; Philip T. Gidley; Andrew D. McQueen; David W. Moore; Deborah A. Edwards; Jeffery Hardenstine; Allen D. Uhler (Archives of Environmental Contamination and Toxicology, 2022)
This is the first investigation of the bioavailability of PCBs associated with paint chips (PC) dispersed in sediment. Bioavailability of PCB-containing PC in sediment was measured using ex situ polyethylene passive samplers (PS) and compared to that of PCBs from field-collected sediments. PC were mixed in freshwater sediment from a relatively uncontaminated site with no known PCB contamination sources and from a contaminated site with non-paint PCB sources. PC

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Estimating fine‐scale movement rates and habitat preferences using multiple data sources - James T. Thorson; Steven J. Barbeaux; Daniel R. Goethel; Kelly A. Kearney; Edward A. Laman; Julie K. Nielsen; Matthew R. Siskey; Kevin Siwicke; Grant G. Thompson (Fish and Fisheries, 2021)
Fisheries scientists and managers must track rapid shifts in fish spatial distribution to mitigate stakeholder conflict and optimize survey designs, and these spatial shifts result in part from animal movement. Information regarding animal movement can be obtained from selection experiments, tagging studies, flux through movement gates (e.g. acoustic arrays), fishery catch‐per‐unit effort (CPUE), resource surveys and genetic/chemical markers. However, there are few accessible approaches to combine these data types while accounting for spatially correlated residual patterns. We therefore discuss a movement model involving diffusion (random movement), taxis (movement towards preferred habitat) and advection (passive drift following ocean currents). We specifically outline how these movement processes can be fitted to data while discretizing space and time and estimating non‐linear habitat preferences using environmental layers as well as spatial process errors. Finally, we introduce an R package, ATM, by fitting the model to bottom trawl survey, longline fishery and tagging data for Pacific cod ( Gadus macrocephalus , Gadidae) in the Bering Sea during winter/summer seasons from 1982 to 2019. Combining data types predicts an increasing proportion of cod residing in the northern Bering Sea from 2013 to 2019, and estimates are informative in a recent stock assessment model. We fit sensitivity analyses by dropping tag, survey or fishery data, and this analysis shows that tagging data are necessary to identify diffusion rates, while survey data are informative about movement among biogeographic strata. This “hybrid” species distribution model can help explain poleward movement, project distributions under future climate conditions and evaluate alternative tag‐deployment scenarios to optimize tagging designs.

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Revisiting the Colletotrichum species causing anthracnose of almond in Australia - D. D. de Silva; R. C. Mann; J. Kaur; P. N Ekanayake; T. I Sawbridge; S. McKay; P. W. J. Taylor; J. Edwards (Australasian Plant Pathology, 2021)

Changes in gastrointestinal cell integrity after marathon running and exercise-associated collapse - Edward Walter; Oliver R. Gibson; Michael Stacey; Neil Hill; Iain T. Parsons; David Woods (European Journal of Applied Physiology, 2021)

Genetic analysis of endometriosis and depression identifies shared loci and implicates causal links with gastric mucosa abnormality - Emmanuel O. Adewuyi; Divya Mehta; Yadav Sapkota; Yadav Sapkota; Kosuke Yoshihara; Mette Nyegaard; Valgerdur Steinthorsdottir; Andrew P. Morris; Amelie Fassbender; Nilufer Rahmioglu; Immaculata De Vivo; Julie E. Buring; et al. (Human Genetics, 2021)

Pantropical variability in tree crown allometry - Grace Jopaul Loubota Panzou; Adeline Fayolle; Tommaso Jucker; Oliver L. Phillips; Stephanie Bohlman; Lindsay F. Banin; Simon L. Lewis; Kofi Affum‐Baffoe; Luciana F. Alves; Cécile Antin; Eric Arets; Luzmila Arroyo; et al. (Global Ecology and Biogeography, 2021)
Aim Tree crowns determine light interception, carbon and water exchange. Thus, understanding the factors causing tree crown allometry to vary at the tree and stand level matters greatly for the development of future vegetation modelling and for the calibration of remote sensing products. Nevertheless, we know little about large‐scale variation and determinants in tropical tree crown allometry. In this study, we explored the continental variation in scaling exponents of site‐specific crown allometry and assessed their relationships with environmental and stand‐level variables in the tropics. Location Global tropics. Time period Early 21st century. Major taxa studied Woody plants. Methods Using a dataset of 87,737 trees distributed among 245 forest and savanna sites across the tropics, we fitted site‐specific allometric relationships between crown dimensions (crown depth, diameter and volume) and stem diameter using power‐law models. Stand‐level and environmental drivers of crown allometric relationships were assessed at pantropical and continental scales. Results The scaling exponents of allometric relationships between stem diameter and crown dimensions were higher in savannas than in forests. We identified that continental crown models were better than pantropical crown models and that continental differences in crown allometric relationships were driven by both stand‐level (wood density) and environmental (precipitation, cation exchange capacity and soil texture) variables for both tropical biomes. For a given diameter, forest trees from Asia and savanna trees from Australia had smaller crown dimensions than trees in Africa and America, with crown volumes for some Asian forest trees being smaller than those of trees in African forests. Main conclusions Our results provide new insight into geographical variability, with large continental differences in tropical tree crown allometry that were driven by stand‐level and environmental variables. They have implications for the assessment of ecosystem function and for the monitoring of woody biomass by remote sensing techniques in the global tropics.

A global analysis of complexity–biodiversity relationships on marine artificial structures - Elisabeth M. A. Strain; Peter D. Steinberg; Maria Vozzo; Emma L. Johnston; Marco Abbiati; Moises A. Aguilera; Laura Airoldi; J. David Aguirre; Gail Ashton; Maritina Bernardi; Paul Brooks; Benny K. K. Chan; et al. (Global Ecology and Biogeography, 2021)
Aim Topographic complexity is widely accepted as a key driver of biodiversity, but at the patch‐scale, complexity–biodiversity relationships may vary spatially and temporally according to the environmental stressors complexity mitigates, and the species richness and identity of potential colonists. Using a manipulative experiment, we assessed spatial variation in patch‐scale effects of complexity on intertidal biodiversity. Location 27 sites within 14 estuaries/bays distributed globally. Time period 2015–2017. Major taxa studied Functional groups of algae, sessile and mobile invertebrates. Methods Concrete tiles of differing complexity (flat; 2.5‐cm or 5‐cm complex) were affixed at low–high intertidal elevation on coastal defence structures, and the richness and abundance of the colonizing taxa were quantified after 12 months. Results The patch‐scale effects of complexity varied spatially and among functional groups. Complexity had neutral to positive effects on total, invertebrate and algal taxa richness, and invertebrate abundances. However, effects on the abundance of algae ranged from positive to negative, depending on location and functional group. The tidal elevation at which tiles were placed accounted for some variation. The total and invertebrate richness were greater at low or mid than at high intertidal elevations. Latitude was also an important source of spatial variation, with the effects of complexity on total richness and mobile mollusc abundance greatest at lower latitudes, whilst the cover of sessile invertebrates and sessile molluscs responded most strongly to complexity at higher latitudes. Conclusions After 12 months, patch‐scale relationships between biodiversity and habitat complexity were not universally positive. Instead, the relationship varied among functional groups and according to local abiotic and biotic conditions. This result challenges the assumption that effects of complexity on biodiversity are universally positive. The variable effect of complexity has ramifications for community and applied ecology, including eco‐engineering and restoration that seek to bolster biodiversity through the addition of complexity.

Greater topoclimatic control of above‐ versus below‐ground communities - Heidi K. Mod; Daniel Scherrer; Valeria Di Cola; Olivier Broennimann; Quentin Blandenier; Frank T. Breiner; Aline Buri; Jérôme Goudet; Nicolas Guex; Enrique Lara; Edward A. D. Mitchell; Hélène Niculita‐Hirzel; et al. (Global Change Biology, 2020)
Assessing the degree to which climate explains the spatial distributions of different taxonomic and functional groups is essential for anticipating the effects of climate change on ecosystems. Most effort so far has focused on above‐ground organisms, which offer only a partial view on the response of biodiversity to environmental gradients. Here including both above‐ and below‐ground organisms, we quantified the degree of topoclimatic control on the occurrence patterns of >1,500 taxa and phylotypes along a c. 3,000 m elevation gradient, by fitting species distribution models. Higher model performances for animals and plants than for soil microbes (fungi, bacteria and protists) suggest that the direct influence of topoclimate is stronger on above‐ground species than on below‐ground microorganisms. Accordingly, direct climate change effects are predicted to be stronger for above‐ground than for below‐ground taxa, whereas factors expressing local soil microclimate and geochemistry are likely more important to explain and forecast the occurrence patterns of soil microbiota. Detailed mapping and future scenarios of soil microclimate and microhabitats, together with comparative studies of interacting and ecologically dependent above‐ and below‐ground biota, are thus needed to understand and realistically forecast the future distribution of ecosystems.

Understanding Naloxone Uptake from an Emergency Department Distribution Program Using a Low-Energy Bluetooth Real-time Location System - Jeffrey T. Lai; Brittany P. Chapman; Stephanie P. Carreiro; Kavita M. Babu; Edward W. Boyer; Peter R. Chai (Journal of Medical Toxicology, 2020)

Evidence for craniofacial enhancer variation underlying nonsyndromic cleft lip and palate - Vershanna E. Morris; S. Shahrukh Hashmi; Lisha Zhu; Lorena Maili; Christian Urbina; Steven Blackwell; Matthew R. Greives; Edward P. Buchanan; John B. Mulliken; Susan H. Blanton; W. Jim Zheng; Jacqueline T. Hecht; et al. (Human Genetics, 2020)

Old growth Afrotropical forests critical for maintaining forest carbon - John R. Poulsen; Vincent P. Medjibe; Lee J. T. White; Zewei Miao; Ludovic Banak‐Ngok; Chris Beirne; Connie J. Clark; Aida Cuni‐Sanchez; Mathias Disney; Jean‐Louis Doucet; Michelle E. Lee; Simon L. Lewis; et al. (Global Ecology and Biogeography, 2020)
Aim Large trees [≥ 70 cm diameter at breast height (DBH)] contribute disproportionately to aboveground carbon stock (AGC) across the tropics but may be vulnerable to changing climate and human activities. Here we determine the distribution, drivers and threats to large trees and high carbon forest. Location Central Africa. Time period Current. Major taxa studied Trees. Methods Using Gabon's new National Resource Inventory of 104 field sites, AGC was calculated from 67,466 trees from 578 species and 97 genera. Power and Michaelis–Menten models assessed the contribution of large trees to AGC. Environmental and anthropogenic drivers of AGC, large trees, and stand variables were modelled using Akaike’s information criterion (AIC) weights to calculate average regression coefficients for all p ossible models. Results Mean AGC for trees ≥ 10 cm DBH in Gabonese forestlands was 141.7 Mg C/ha, with averages of 166.6, 171.3 and 96.6 Mg C/ha in old growth, concession and secondary forest. High carbon forests occurred where large trees are most abundant: 31% of AGC was stored in large trees (2.3% of all stems). Human activities largely drove variation in AGC and large trees, but climate and edaphic conditions also determined stand variables (basal area, tree height, wood density, stem density). AGC and large trees increased with distance from human settlements; AGC was 40% lower in secondary than primary and concession forests and 33% higher in protected than non‐managed areas. Main conclusions AGC and large trees were negatively associated with human activities, highlighting the importance of forest management. Redefining large trees as ≥ 50 cm DBH (4.3% more stems) would account for 20% more AGC. This study demonstrates that protecting relatively undisturbed forests can be disproportionately effective in conserving carbon and suggests that including sustainable forestry in programs like reduced emissions for deforestation and forest degradation could maintain carbon dense forests in logging concessions that are a large proportion of remaining Central African forests.

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Ensuring tests of conservation interventions build on existing literature - William J. Sutherland; Sergio Ticul Alvarez‐Castañeda; Tatsuya Amano; Roberto Ambrosini; Philip Atkinson; John M. Baxter; Alexander L. Bond; Philip J. Boon; Katherine L. Buchanan; Jos Barlow; Giuseppe Bogliani; Olivia M. Bragg; et al. (Conservation Biology, 2020)

7700-year persistence of an isolated, free-living coral assemblage in the Galápagos Islands: a model for coral refugia? - J. S. Feingold; B. Riegl; K. Hendrickson; L. T. Toth; H. Cheng; R. L. Edwards; R. B. Aronson (Coral Reefs, 2020)

Secondary forest fragments offer important carbon and biodiversity cobenefits - Fabio A. R. Matos; Luiz F. S. Magnago; Carlos Aquila Chan Miranda; Luis F. T. de Menezes; Markus Gastauer; Nathália V. H. Safar; Carlos E. G. R. Schaefer; Mônica P. da Silva; Marcelo Simonelli; Felicity A. Edwards; Sebastião V. Martins; João A. A. Meira‐Neto; et al. (Global Change Biology, 2020)
Tropical forests store large amounts of carbon and high biodiversity, but are being degraded at alarming rates. The emerging global Forest and Landscape Restoration (FLR) agenda seeks to limit global climate change by removing carbon dioxide from the atmosphere through the growth of trees. In doing so, it may also protect biodiversity as a free cobenefit, which is vital given the massive shortfall in funding for biodiversity conservation. We investigated whether natural forest regeneration on abandoned pastureland offers such cobenefits, focusing for the first time on the recovery of taxonomic diversity (TD), phylogenetic diversity (PD) and functional diversity (FD) of trees, including the recovery of threatened and endemic species richness, within isolated secondary forest (SF) fragments. We focused on the globally threatened Brazilian Atlantic Forest, where commitments have been made to restore 1 million hectares under FLR. Three decades after land abandonment, regenerating forests had recovered ~20% (72 Mg/ha) of the above‐ground carbon stocks of a primary forest (PF), with cattle pasture containing just 3% of stocks relative to PFs. Over this period, SF recovered ~76% of TD, 84% of PD and 96% of FD found within PFs. In addition, SFs had on average recovered 65% of threatened and ~30% of endemic species richness of primary Atlantic forest. Finally, we find positive relationships between carbon stock and tree diversity recovery. Our results emphasize that SF fragments offer cobenefits under FLR and other carbon‐based payments for ecosystem service schemes (e.g. carbon enhancements under REDD+). They also indicate that even isolated patches of SF could help to mitigate climate change and the biodiversity extinction crisis by recovering species of high conservation concern and improving landscape connectivity.

Blue Carbon: an Additional Driver for Restoring and Preserving Ecological Services of Coastal Wetlands in Tampa Bay (Florida, USA) - Lindsey Sheehan; Edward T. Sherwood; Ryan P. Moyer; Kara R. Radabaugh; Stefanie Simpson (Wetlands, 2019)

Improving the diagnostic accuracy of a stratified screening strategy by identifying the optimal risk cutoff - John T. Brinton; R. Edward Hendrick; Brandy M. Ringham; Mieke Kriege; Deborah H. Glueck (Cancer Causes & Control, 2019)

Environmental heterogeneity and not vicariant biogeographic barriers generate community‐wide population structure in desert‐adapted snakes - Edward A. Myers; Alexander T. Xue; Marcelo Gehara; Christian L. Cox; Alison R. Davis Rabosky; Julio Lemos‐Espinal; Juan E. Martínez‐Gómez; Frank T. Burbrink (Molecular Ecology, 2019)
Genetic structure can be influenced by local adaptation to environmental heterogeneity and biogeographic barriers, resulting in discrete population clusters. Geographic distance among populations, however, can result in continuous clines of genetic divergence that appear as structured populations. Here, we evaluate the relevant importance of these three factors over a landscape characterized by environmental heterogeneity and the presence of a hypothesized biogeographic barrier in producing population genetic structure within 13 codistributed snake species using a genomic data set. We demonstrate that geographic distance and environmental heterogeneity across western North America contribute to population genomic divergence. Surprisingly, landscape features long thought to contribute to biogeographic barriers play little role in divergence community wide. Our results suggest that isolation by environment is the most important contributor to genomic divergence. Furthermore, we show that models of population clustering that incorporate spatial information consistently outperform nonspatial models, demonstrating the importance of considering geographic distances in population clustering. We argue that environmental and geographic distances as drivers of community‐wide divergence should be explored before assuming the role of biogeographic barriers.

Toward the Integrated Marine Debris Observing System - Nikolai Maximenko; Paolo Corradi; Kara Lavender Law; Erik Van Sebille; Shungudzemwoyo P. Garaba; Richard Stephen Lampitt; Francois Galgani; Victor Martinez-Vicente; Lonneke Goddijn-Murphy; Joana Mira Veiga; Richard C. Thompson; Christophe Maes; et al. (Frontiers in Marine Science, 2019)

Modeling Environmental DNA Transport in the Coastal Ocean Using Lagrangian Particle Tracking - Elizabeth A. Andruszkiewicz; Jeffrey R. Koseff; Oliver B. Fringer; Nicholas T. Ouellette; Anna B. Lowe; Christopher A. Edwards; Alexandria B. Boehm (Frontiers in Marine Science, 2019)

A Global Plankton Diversity Monitoring Program - Sonia D. Batten; Rana Abu-Alhaija; Sanae Chiba; Martin Edwards; George Graham; R. Jyothibabu; John A. Kitchener; Philippe Koubbi; Abigail McQuatters-Gollop; Erik Muxagata; Clare Ostle; Anthony J. Richardson; et al. (Frontiers in Marine Science, 2019)

Modeling Temperature Regime and Physical Habitat Impacts from Restored Streamflow - Russell T. Bair; Benjamin W. Tobin; Brian D. Healy; Claire E. Spangenberg; Hampton K. Childres; Edward R. Schenk (Environmental Management, 2019)

Multi-level emulation of complex climate model responses to boundary forcing data - Giang T. Tran; Kevin I. C. Oliver; Philip B. Holden; Neil R. Edwards; András Sóbester; Peter Challenor (Climate Dynamics, 2019)

Biotic responses buffer warming‐induced soil organic carbon loss in Arctic tundra - Junyi Liang; Jiangyang Xia; Zheng Shi; Lifen Jiang; Shuang Ma; Xingjie Lu; Marguerite Mauritz; Susan M. Natali; Elaine Pegoraro; Christopher Ryan Penton; César Plaza; Verity G. Salmon; et al. (Global Change Biology, 2018)
Climate warming can result in both abiotic (e.g., permafrost thaw) and biotic (e.g., microbial functional genes) changes in Arctic tundra. Recent research has incorporated dynamic permafrost thaw in Earth system models ( ESM s) and indicates that Arctic tundra could be a significant future carbon (C) source due to the enhanced decomposition of thawed deep soil C. However, warming‐induced biotic changes may influence biologically related parameters and the consequent projections in ESM s. How model parameters associated with biotic responses will change under warming and to what extent these changes affect projected C budgets have not been carefully examined. In this study, we synthesized six data sets over 5 years from a soil warming experiment at the Eight Mile Lake, Alaska, into the Terrestrial ECO system ( TECO ) model with a probabilistic inversion approach. The TECO model used multiple soil layers to track dynamics of thawed soil under different treatments. Our results show that warming increased light use efficiency of vegetation photosynthesis but decreased baseline (i.e., environment‐corrected) turnover rates of SOC in both the fast and slow pools in comparison with those under control. Moreover, the parameter changes generally amplified over time, suggesting processes of gradual physiological acclimation and functional gene shifts of both plants and microbes. The TECO model predicted that field warming from 2009 to 2013 resulted in cumulative C losses of 224 or 87 g/m 2 , respectively, without or with changes in those parameters. Thus, warming‐induced parameter changes reduced predicted soil C loss by 61%. Our study suggests that it is critical to incorporate biotic changes in ESM s to improve the model performance in predicting C dynamics in permafrost regions.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Interactions among plants, bacteria, and fungi reduce extracellular enzyme activities under long‐term N fertilization - Joseph E. Carrara; Christopher A. Walter; Jennifer S. Hawkins; William T. Peterjohn; Colin Averill; Edward R. Brzostek (Global Change Biology, 2018)
Atmospheric nitrogen (N) deposition has enhanced soil carbon (C) stocks in temperate forests. Most research has posited that these soil C gains are driven primarily by shifts in fungal community composition with elevated N leading to declines in lignin degrading Basidiomycetes . Recent research, however, suggests that plants and soil microbes are dynamically intertwined, whereby plants send C subsidies to rhizosphere microbes to enhance enzyme production and the mobilization of N. Thus, under elevated N, trees may reduce belowground C allocation leading to cascading impacts on the ability of microbes to degrade soil organic matter through a shift in microbial species and/or a change in plant–microbe interactions. The objective of this study was to determine the extent to which couplings among plant, fungal, and bacterial responses to N fertilization alter the activity of enzymes that are the primary agents of soil decomposition. We measured fungal and bacterial community composition, root–microbial interactions, and extracellular enzyme activity in the rhizosphere, bulk, and organic horizon of soils sampled from a long‐term (>25 years), whole‐watershed, N fertilization experiment at the Fernow Experimental Forest in West Virginia, USA. We observed significant declines in plant C investment to fine root biomass (24.7%), root morphology, and arbuscular mycorrhizal (AM) colonization (55.9%). Moreover, we found that declines in extracellular enzyme activity were significantly correlated with a shift in bacterial community composition, but not fungal community composition. This bacterial community shift was also correlated with reduced AM fungal colonization indicating that declines in plant investment belowground drive the response of bacterial community structure and function to N fertilization. Collectively, we find that enzyme activity responses to N fertilization are not solely driven by fungi, but instead reflect a whole ecosystem response, whereby declines in the strength of belowground C investment to gain N cascade through the soil environment.

Ecosystem state shifts during long‐term development of an Amazonian peatland - Graeme T. Swindles; Paul J. Morris; Bronwen Whitney; Jennifer M. Galloway; Mariusz Gałka; Angela Gallego‐Sala; Andrew L. Macumber; Donal Mullan; Mark W. Smith; Matthew J. Amesbury; Thomas P. Roland; Hamed Sanei; et al. (Global Change Biology, 2018)
The most carbon (C)‐dense ecosystems of Amazonia are areas characterized by the presence of peatlands. However, Amazonian peatland ecosystems are poorly understood and are threatened by human activities. Here, we present an investigation into long‐term ecohydrological controls on C accumulation in an Amazonian peat dome. This site is the oldest peatland yet discovered in Amazonia (peat initiation ca. 8.9 ka BP ), and developed in three stages: (i) peat initiated in an abandoned river channel with open water and aquatic plants; (ii) inundated forest swamp; and (iii) raised peat dome (since ca. 3.9 ka BP ). Local burning occurred at least three times in the past 4,500 years. Two phases of particularly rapid C accumulation (ca. 6.6–6.1 and ca. 4.9–3.9 ka BP ), potentially resulting from increased net primary productivity, were seemingly driven by drier conditions associated with widespread drought events. The association of drought phases with major ecosystem state shifts (open water wetland–forest swamp–peat dome) suggests a potential climatic control on the developmental trajectory of this tropical peatland. A third drought phase centred on ca. 1.8–1.1 ka BP led to markedly reduced C accumulation and potentially a hiatus during the peat dome stage. Our results suggest that future droughts may lead to phases of rapid C accumulation in some inundated tropical peat swamps, although this can lead ultimately to a shift to ombrotrophy and a subsequent return to slower C accumulation. Conversely, in ombrotrophic peat domes, droughts may lead to reduced C accumulation or even net loss of peat. Increased surface wetness at our site in recent decades may reflect a shift towards a wetter climate in western Amazonia. Amazonian peatlands represent important carbon stores and habitats, and are important archives of past climatic and ecological information. They should form key foci for conservation efforts.

SDF-1 induces TNF-mediated apoptosis in cardiac myocytes - Andrew A. Jarrah; Martina Schwarskopf; Edward R. Wang; Thomas LaRocca; Ashwini Dhume; Shihong Zhang; Lahouria Hadri; Roger J. Hajjar; Alison D. Schecter; Sima T. Tarzami (Apoptosis, 2018)

Microbial functional diversity covaries with permafrost thaw‐induced environmental heterogeneity in tundra soil - Mengting M. Yuan; Jin Zhang; Kai Xue; Liyou Wu; Ye Deng; Jie Deng; Lauren Hale; Xishu Zhou; Zhili He; Yunfeng Yang; Joy D. Van Nostrand; Edward A. G. Schuur; et al. (Global Change Biology, 2018)
Permafrost soil in high latitude tundra is one of the largest terrestrial carbon (C) stocks and is highly sensitive to climate warming. Understanding microbial responses to warming‐induced environmental changes is critical to evaluating their influences on soil biogeochemical cycles. In this study, a functional gene array (i.e., geochip 4.2) was used to analyze the functional capacities of soil microbial communities collected from a naturally degrading permafrost region in Central Alaska. Varied thaw history was reported to be the main driver of soil and plant differences across a gradient of minimally, moderately, and extensively thawed sites. Compared with the minimally thawed site, the number of detected functional gene probes across the 15–65 cm depth profile at the moderately and extensively thawed sites decreased by 25% and 5%, while the community functional gene β‐diversity increased by 34% and 45%, respectively, revealing decreased functional gene richness but increased community heterogeneity along the thaw progression. Particularly, the moderately thawed site contained microbial communities with the highest abundances of many genes involved in prokaryotic C degradation, ammonification, and nitrification processes, but lower abundances of fungal C decomposition and anaerobic‐related genes. Significant correlations were observed between functional gene abundance and vascular plant primary productivity, suggesting that plant growth and species composition could be co‐evolving traits together with microbial community composition. Altogether, this study reveals the complex responses of microbial functional potentials to thaw‐related soil and plant changes and provides information on potential microbially mediated biogeochemical cycles in tundra ecosystems.

Asynchrony among local communities stabilises ecosystem function of metacommunities - Kevin R. Wilcox; Andrew T. Tredennick; Sally E. Koerner; Emily Grman; Lauren M. Hallett; Meghan L. Avolio; Kimberly J. La Pierre; Gregory R. Houseman; Forest Isbell; David Samuel Johnson; Juha M. Alatalo; Andrew H. Baldwin; et al. (Ecology Letters, 2017)
Temporal stability of ecosystem functioning increases the predictability and reliability of ecosystem services, and understanding the drivers of stability across spatial scales is important for land management and policy decisions. We used species‐level abundance data from 62 plant communities across five continents to assess mechanisms of temporal stability across spatial scales. We assessed how asynchrony (i.e. different units responding dissimilarly through time) of species and local communities stabilised metacommunity ecosystem function. Asynchrony of species increased stability of local communities, and asynchrony among local communities enhanced metacommunity stability by a wide range of magnitudes (1–315%); this range was positively correlated with the size of the metacommunity. Additionally, asynchronous responses among local communities were linked with species’ populations fluctuating asynchronously across space, perhaps stemming from physical and/or competitive differences among local communities. Accordingly, we suggest spatial heterogeneity should be a major focus for maintaining the stability of ecosystem services at larger spatial scales.

Asymmetric responses of primary productivity to precipitation extremes: A synthesis of grassland precipitation manipulation experiments - Kevin R. Wilcox; Zheng Shi; Laureano A. Gherardi; Nathan P. Lemoine; Sally E. Koerner; David L. Hoover; Edward Bork; Kerry M. Byrne; James Cahill; Scott L. Collins; Sarah Evans; Anna K. Gilgen; et al. (Global Change Biology, 2017)
Climatic changes are altering Earth's hydrological cycle, resulting in altered precipitation amounts, increased interannual variability of precipitation, and more frequent extreme precipitation events. These trends will likely continue into the future, having substantial impacts on net primary productivity ( NPP ) and associated ecosystem services such as food production and carbon sequestration. Frequently, experimental manipulations of precipitation have linked altered precipitation regimes to changes in NPP . Yet, findings have been diverse and substantial uncertainty still surrounds generalities describing patterns of ecosystem sensitivity to altered precipitation. Additionally, we do not know whether previously observed correlations between NPP and precipitation remain accurate when precipitation changes become extreme. We synthesized results from 83 case studies of experimental precipitation manipulations in grasslands worldwide. We used meta‐analytical techniques to search for generalities and asymmetries of aboveground NPP ( ANPP ) and belowground NPP ( BNPP ) responses to both the direction and magnitude of precipitation change. Sensitivity (i.e., productivity response standardized by the amount of precipitation change) of BNPP was similar under precipitation additions and reductions, but ANPP was more sensitive to precipitation additions than reductions; this was especially evident in drier ecosystems. Additionally, overall relationships between the magnitude of productivity responses and the magnitude of precipitation change were saturating in form. The saturating form of this relationship was likely driven by ANPP responses to very extreme precipitation increases, although there were limited studies imposing extreme precipitation change, and there was considerable variation among experiments. This highlights the importance of incorporating gradients of manipulations, ranging from extreme drought to extreme precipitation increases into future climate change experiments. Additionally, policy and land management decisions related to global change scenarios should consider how ANPP and BNPP responses may differ, and that ecosystem responses to extreme events might not be predicted from relationships found under moderate environmental changes.

15N recoveries from ruminant urine patches on three forage types - R. R. Woods; K. C. Cameron; G. R. Edwards; H. J. Di; T. J. Clough (Plant and Soil, 2017)

Greater temperature sensitivity of plant phenology at colder sites: implications for convergence across northern latitudes - Janet Prevéy; Mark Vellend; Nadja Rüger; Robert D. Hollister; Anne D. Bjorkman; Isla H. Myers‐Smith; Sarah C. Elmendorf; Karin Clark; Elisabeth J. Cooper; Bo Elberling; Anna M. Fosaa; Gregory H. R. Henry; et al. (Global Change Biology, 2017)
Warmer temperatures are accelerating the phenology of organisms around the world. Temperature sensitivity of phenology might be greater in colder, higher latitude sites than in warmer regions, in part because small changes in temperature constitute greater relative changes in thermal balance at colder sites. To test this hypothesis, we examined up to 20 years of phenology data for 47 tundra plant species at 18 high‐latitude sites along a climatic gradient. Across all species, the timing of leaf emergence and flowering was more sensitive to a given increase in summer temperature at colder than warmer high‐latitude locations. A similar pattern was seen over time for the flowering phenology of a widespread species, Cassiope tetragona . These are among the first results highlighting differential phenological responses of plants across a climatic gradient and suggest the possibility of convergence in flowering times and therefore an increase in gene flow across latitudes as the climate warms.

Role of polysaccharides in food, digestion, and health - A. Lovegrove; C. H. Edwards; I. De Noni; H. Patel; S. N. El; T. Grassby; C. Zielke; M. Ulmius; L. Nilsson; P. J. Butterworth; P. R Ellis; P. R. Shewry (Critical Reviews in Food Science and Nutrition, 2017)

Primate genotyping via high resolution melt analysis: rapid and reliable identification of color vision status in wild lemurs - Rachel L. Jacobs; Amanda N. Spriggs; Tammie S. MacFie; Andrea L. Baden; Mitchell T. Irwin; Patricia C. Wright; Edward E. Louis; Richard R. Lawler; Nicholas I. Mundy; Brenda J. Bradley (Primates, 2016)

Colletotrichum species in Australia - Roger G. Shivas; Yu Pei Tan; Jacqueline Edwards; Quang Dinh; Aaron Maxwell; Vera Andjic; José R. Liberato; Chris Anderson; Dean R. Beasley; Kaylene Bransgrove; Lindy M. Coates; Karren Cowan; et al. (Australasian Plant Pathology, 2016)

Use of a coupled soil-root-leaf model to optimise phosphate fertiliser use efficiency in barley - J. Heppell; S. Payvandi; P. Talboys; K. C. Zygalakis; D. Langton; R. Sylvester-Bradley; A. C. Edwards; R. Walker; P. Withers; D. L. Jones; T. Roose (Plant and Soil, 2016)

Intramuscular MAPK signaling following high volume and high intensity resistance exercise protocols in trained men - Adam M. Gonzalez; Jay R. Hoffman; Jeremy R. Townsend; Adam R. Jajtner; Carleigh H. Boone; Kyle S. Beyer; Kayla M. Baker; Adam J. Wells; Gerald T. Mangine; Edward H. Robinson; David D. Church; Leonardo P. Oliveira; et al. (European Journal of Applied Physiology, 2016)

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

Subglacial lava propagation, ice melting and heat transfer during emplacement of an intermediate lava flow in the 2010 Eyjafjallajökull eruption - Björn Oddsson; Magnús T. Gudmundsson; Benjamin R. Edwards; Thorvaldur Thordarson; Eyjólfur Magnússon; Gunnar Sigurðsson (Bulletin of Volcanology, 2016)

Tree‐mycorrhizal associations detected remotely from canopy spectral properties - Joshua B. Fisher; Sean Sweeney; Edward R. Brzostek; Tom P. Evans; Daniel J. Johnson; Jonathan A. Myers; Norman A. Bourg; Amy T. Wolf; Robert W. Howe; Richard P. Phillips (Global Change Biology, 2016)
A central challenge in global ecology is the identification of key functional processes in ecosystems that scale, but do not require, data for individual species across landscapes. Given that nearly all tree species form symbiotic relationships with one of two types of mycorrhizal fungi – arbuscular mycorrhizal ( AM ) and ectomycorrhizal ( ECM ) fungi – and that AM ‐ and ECM ‐dominated forests often have distinct nutrient economies, the detection and mapping of mycorrhizae over large areas could provide valuable insights about fundamental ecosystem processes such as nutrient cycling, species interactions, and overall forest productivity. We explored remotely sensed tree canopy spectral properties to detect underlying mycorrhizal association across a gradient of AM ‐ and ECM ‐dominated forest plots. Statistical mining of reflectance and reflectance derivatives across moderate/high‐resolution Landsat data revealed distinctly unique phenological signals that differentiated AM and ECM associations. This approach was trained and validated against measurements of tree species and mycorrhizal association across ~130 000 trees throughout the temperate United States. We were able to predict 77% of the variation in mycorrhizal association distribution within the forest plots ( P

Genetic Analysis of the Indri Reveals No Evidence of Distinct Subspecies - Rick A. Brenneman; Adam T. McLain; Justin M. Taylor; John R. Zaonarivelo; Runhua Lei; Susie M. McGuire; Rambinintsoa Andriantompohavana; Anthony B. Rylands; Edward E. Louis (International Journal of Primatology, 2016)

The invertebrate ecology of the Chalk aquifer in England (UK) - L. Maurice; A. R. Robertson; D. White; L. Knight; T. Johns; F. Edwards; M. Arietti; J. P. R. Sorensen; D. Weitowitz; B. P. Marchant; J. P. Bloomfield (Hydrogeology Journal, 2016)

Speciation with gene flow in whiptail lizards from a Neotropical xeric biome - Eliana F. Oliveira; Marcelo Gehara; Vinícius A. São‐Pedro; Xin Chen; Edward A. Myers; Frank T. Burbrink; Daniel O. Mesquita; Adrian A. Garda; Guarino R. Colli; Miguel T. Rodrigues; Federico J. Arias; Hussam Zaher; et al. (Molecular Ecology, 2015)
Two main hypotheses have been proposed to explain the diversification of the Caatinga biota. The riverine barrier hypothesis ( RBH ) claims that the São Francisco River ( SFR ) is a major biogeographic barrier to gene flow. The Pleistocene climatic fluctuation hypothesis ( PCH ) states that gene flow, geographic genetic structure and demographic signatures on endemic Caatinga taxa were influenced by Quaternary climate fluctuation cycles. Herein, we analyse genetic diversity and structure, phylogeographic history, and diversification of a widespread Caatinga lizard ( Cnemidophorus ocellifer ) based on large geographical sampling for multiple loci to test the predictions derived from the RBH and PCH . We inferred two well‐delimited lineages (Northeast and Southwest) that have diverged along the Cerrado–Caatinga border during the Mid‐Late Miocene (6–14 Ma) despite the presence of gene flow. We reject both major hypotheses proposed to explain diversification in the Caatinga. Surprisingly, our results revealed a striking complex diversification pattern where the Northeast lineage originated as a founder effect from a few individuals located along the edge of the Southwest lineage that eventually expanded throughout the Caatinga. The Southwest lineage is more diverse, older and associated with the Cerrado–Caatinga boundaries. Finally, we suggest that C. ocellifer from the Caatinga is composed of two distinct species. Our data support speciation in the presence of gene flow and highlight the role of environmental gradients in the diversification process.

The novel mu-opioid antagonist, GSK1521498, reduces ethanol consumption in C57BL/6J mice - Tamzin L. Ripley; Sandra Sanchez-Roige; Edward T. Bullmore; Manolo Mugnaini; Kay Maltby; Sam R. Miller; David R. Wille; Pradeep Nathan; David N. Stephens (Psychopharmacology, 2015)

Hydrology under change: an evaluation protocol to investigate how hydrological models deal with changing catchments - G. Thirel; V. Andréassian; C. Perrin; J.-N. Audouy; L. Berthet; P. Edwards; N. Folton; C. Furusho; A. Kuentz; J. Lerat; G. Lindström; E. Martin; et al. (Hydrological Sciences Journal, 2015)

Diverse phenotypic consequences of mutations affecting the C-terminus of FLNA - Margriet van Kogelenberg; Alice R. Clark; Zandra Jenkins; Tim Morgan; Ananda Anandan; Gregory M. Sawyer; Matthew Edwards; Tracy Dudding; Tessa Homfray; Bruce Castle; John Tolmie; Fiona Stewart; et al. (Journal of Molecular Medicine, 2015)

Phosphanegold(I) thiolates, Ph3PAu[SC(OR)=NC6H4Me-4] for R = Me, Et and iPr, induce apoptosis, cell cycle arrest and inhibit cell invasion of HT-29 colon cancer cells through modulation of the nuclear factor-κB activation pathway and ubiquitination - Kah Kooi Ooi; Chien Ing Yeo; Kok-Pian Ang; Abdah Md Akim; Yoke-Kqueen Cheah; Siti Nadiah Abdul Halim; Hoi-Ling Seng; Edward R. T. Tiekink (JBIC Journal of Biological Inorganic Chemistry, 2015)

Following Natures Lead: On the Construction of Membrane-Inserted Toxins in Lipid Bilayer Nanodiscs - Narahari Akkaladevi; Srayanta Mukherjee; Hiroo Katayama; Blythe Janowiak; Deepa Patel; Edward P. Gogol; Bradley L. Pentelute; R. John Collier; Mark T. Fisher (The Journal of Membrane Biology, 2015)

Worldwide phylogeography of the invasive ctenophore Mnemiopsis leidyi (Ctenophora) based on nuclear and mitochondrial DNA data - K. M. Bayha; M. H. Chang; C. L. Mariani; J. L. Richardson; D. L. Edwards; T. S. DeBoer; C. Moseley; E. Aksoy; M. B. Decker; P. M. Gaffney; G. R. Harbison; J. H. McDonald; et al. (Biological Invasions, 2015)

Diversity within the genus Elymus (Poaceae: Triticeae) as investigated by the analysis of the nr5S rDNA variation in species with St and H haplomes - B. R. Baum; T. Edwards; D. A. Johnson (Molecular Genetics and Genomics, 2015)

A Multidisciplinary Conceptualization of Conservation Opportunity - KATIE MOON; VANESSA M. ADAMS; STEPHANIE R. JANUCHOWSKI‐HARTLEY; MAKSYM POLYAKOV; MORENA MILLS; DUAN BIGGS; ANDREW T. KNIGHT; EDWARD T. GAME; CHRISTOPHER M. RAYMOND (Conservation Biology, 2014)
An opportunity represents an advantageous combination of circumstances that allows goals to be achieved. We reviewed the nature of opportunity and how it manifests in different subsystems (e.g., biophysical, social, political, economic) as conceptualized in other bodies of literature, including behavior, adoption, entrepreneur, public policy, and resilience literature. We then developed a multidisciplinary conceptualization of conservation opportunity. We identified 3 types of conservation opportunity: potential , actors remove barriers to problem solving by identifying the capabilities within the system that can be manipulated to create support for conservation action; traction , actors identify windows of opportunity that arise from exogenous shocks, events, or changes that remove barriers to solving problems; and existing , everything is in place for conservation action (i.e., no barriers exist) and an actor takes advantage of the existing circumstances to solve problems. Different leverage points characterize each type of opportunity. Thus, unique stages of opportunity identification or creation and exploitation exist: characterizing the system and defining problems; identifying potential solutions; assessing the feasibility of solutions; identifying or creating opportunities; and taking advantage of opportunities. These stages can be undertaken independently or as part of a situational analysis and typically comprise the first stage, but they can also be conducted iteratively throughout a conservation planning process. Four types of entrepreneur can be identified (business, policy, social, and conservation), each possessing attributes that enable them to identify or create opportunities and take advantage of them. We examined how different types of conservation opportunity manifest in a social–ecological system (the Great Barrier Reef) and how they can be taken advantage of. Our multidisciplinary conceptualization of conservation opportunity strengthens and legitimizes the concept.

Neuroendocrine and sympathetic responses to an orexin receptor antagonist, SB-649868, and Alprazolam following insulin-induced hypoglycemia in humans - Ameera X. Patel; Sam R. Miller; Pradeep J. Nathan; Ponmani Kanakaraj; Antonella Napolitano; Philip Lawrence; Annelize Koch; Edward T. Bullmore (Psychopharmacology, 2014)

Functional analysis reveals angiogenic potential of human mesenchymal stem cells from Wharton’s jelly in dermal regeneration - Sandra S. Edwards; Gabriela Zavala; Catalina P. Prieto; Matías Elliott; Samuel Martínez; Jose T. Egaña; María R. Bono; Verónica Palma (Angiogenesis, 2014)

What does the nr5S DNA multigene family tell us about the genomic relationship between Dasypyrum breviaristatum and D. villosum (Triticeae: Poaceae)? - B. R. Baum; T. Edwards; D. A. Johnson (Molecular Genetics and Genomics, 2014)

Markedly divergent estimates of A mazon forest carbon density from ground plots and satellites - Edward T. A. Mitchard; Ted R. Feldpausch; Roel J. W. Brienen; Gabriela Lopez‐Gonzalez; Abel Monteagudo; Timothy R. Baker; Simon L. Lewis; Jon Lloyd; Carlos A. Quesada; Manuel Gloor; Hans ter Steege; Patrick Meir; et al. (Global Ecology and Biogeography, 2014)
Aim The accurate mapping of forest carbon stocks is essential for understanding the global carbon cycle, for assessing emissions from deforestation, and for rational land‐use planning. Remote sensing ( RS ) is currently the key tool for this purpose, but RS does not estimate vegetation biomass directly, and thus may miss significant spatial variations in forest structure. We test the stated accuracy of pantropical carbon maps using a large independent field dataset. Location Tropical forests of the A mazon basin. The permanent archive of the field plot data can be accessed at: http://dx.doi.org/10.5521/FORESTPLOTS.NET/2014_1 Methods Two recent pantropical RS maps of vegetation carbon are compared to a unique ground‐plot dataset, involving tree measurements in 413 large inventory plots located in nine countries. The RS maps were compared directly to field plots, and kriging of the field data was used to allow area‐based comparisons. Results The two RS carbon maps fail to capture the main gradient in Amazon forest carbon detected using 413 ground plots, from the densely wooded tall forests of the north‐east, to the light‐wooded, shorter forests of the south‐west. The differences between plots and RS maps far exceed the uncertainties given in these studies, with whole regions over‐ or under‐estimated by > 25%, whereas regional uncertainties for the maps were reported to be Main conclusions Pantropical biomass maps are widely used by governments and by projects aiming to reduce deforestation using carbon offsets, but may have significant regional biases. Carbon‐mapping techniques must be revised to account for the known ecological variation in tree wood density and allometry to create maps suitable for carbon accounting. The use of single relationships between tree canopy height and above‐ground biomass inevitably yields large, spatially correlated errors. This presents a significant challenge to both the forest conservation and remote sensing communities, because neither wood density nor species assemblages can be reliably mapped from space.

The land-ice contribution to 21st-century dynamic sea level rise - T. Howard; J. Ridley; A. K. Pardaens; R. T. W. L. Hurkmans; A. J. Payne; R. H. Giesen; J. A. Lowe; J. L. Bamber; T. L. Edwards; J. Oerlemans (Ocean Science, 2014)
Climate change has the potential to influence global mean sea level through a number of processes including (but not limited to) thermal expansion of the oceans and enhanced land ice melt. In addition to their contribution to global mean sea level change, these two processes (among others) lead to local departures from the global mean sea level change, through a number of mechanisms including the effect on spatial variations in the change of water density and transport, usually termed dynamic sea level changes. In this study, we focus on the component of dynamic sea level change that might be given by additional freshwater inflow to the ocean under scenarios of 21st-century land-based ice melt. We present regional patterns of dynamic sea level change given by a global-coupled atmosphere–ocean climate model forced by spatially and temporally varying projected ice-melt fluxes from three sources: the Antarctic ice sheet, the Greenland Ice Sheet and small glaciers and ice caps. The largest ice melt flux we consider is equivalent to almost 0.7 m of global mean sea level rise over the 21st century. The temporal evolution of the dynamic sea level changes, in the presence of considerable variations in the ice melt flux, is also analysed. We find that the dynamic sea level change associated with the ice melt is small, with the largest changes occurring in the North Atlantic amounting to 3 cm above the global mean rise. Furthermore, the dynamic sea level change associated with the ice melt is similar regardless of whether the simulated ice fluxes are applied to a simulation with fixed CO2 or under a business-as-usual greenhouse gas warming scenario of increasing CO2.

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

Interactions of time of day and sleep with between-session habituation and extinction memory in young adult males - Edward F. Pace-Schott; Lauren E. Tracy; Zoe Rubin; Adrian G. Mollica; Jeffrey M. Ellenbogen; Matt T. Bianchi; Mohammed R. Milad; Roger K. Pitman; Scott P. Orr (Experimental Brain Research, 2014)

Priority research questions for the UK food system - John S. I. Ingram; Hugh L. Wright; Lucy Foster; Timothy Aldred; David Barling; Tim G. Benton; Paul M. Berryman; Charles S. Bestwick; Alice Bows-Larkin; Tim F. Brocklehurst; Judith Buttriss; John Casey; et al. (Food Security, 2013)
The rise of food security up international political, societal and academic agendas has led to increasing interest in novel means of improving primary food production and reducing waste. There are however, also many ‘post-farm gate’ activities that are critical to food security, including processing, packaging, distributing, retailing, cooking and consuming. These activities all affect a range of important food security elements, notably availability, affordability and other aspects of access, nutrition and safety. Addressing the challenge of universal food security, in the context of a number of other policy goals (e.g. social, economic and environmental sustainability), is of keen interest to a range of UK stakeholders but requires an up-to-date evidence base and continuous innovation. An exercise was therefore conducted, under the auspices of the UK Global Food Security Programme, to identify priority research questions with a focus on the UK food system (though the outcomes may be broadly applicable to other developed nations). Emphasis was placed on incorporating a wide range of perspectives (‘world views’) from different stakeholder groups: policy, private sector, non-governmental organisations, advocacy groups and academia. A total of 456 individuals submitted 820 questions from which 100 were selected by a process of online voting and a three-stage workshop voting exercise. These 100 final questions were sorted into 10 themes and the ‘top’ question for each theme identified by a further voting exercise. This step also allowed four different stakeholder groups to select the top 7–8 questions from their perspectives. Results of these voting exercises are presented. It is clear from the wide range of questions prioritised in this exercise that the different stakeholder groups identified specific research needs on a range of post-farm gate activities and food security outcomes. Evidence needs related to food affordability, nutrition and food safety (all key elements of food security) featured highly in the exercise. While there were some questions relating to climate impacts on production, other important topics for food security (e.g. trade, transport, preference and cultural needs) were not viewed as strongly by the participants.

Attenuation of cocaine and heroin seeking by μ-opioid receptor antagonism - Chiara Giuliano; Trevor W. Robbins; David R. Wille; Edward T. Bullmore; Barry J. Everitt (Psychopharmacology, 2013)

Polymorphisms in genes related to one-carbon metabolism are not related to pancreatic cancer in PanScan and PanC4 - Max Leenders; Samsiddhi Bhattacharjee; Paolo Vineis; Victoria Stevens; H. Bas Bueno-de-Mesquita; Xiao-Ou Shu; Laufey Amundadottir; Myron Gross; Geoffrey S. Tobias; Jean Wactawski-Wende; Alan A. Arslan; Eric J. Duell; et al. (Cancer Causes & Control, 2013)

Effects of mu opioid receptor antagonism on cognition in obese binge-eating individuals - Samuel R. Chamberlain; Karin Mogg; Brendan P. Bradley; Annelize Koch; Chris M. Dodds; Wenli X. Tao; Kay Maltby; Bhopinder Sarai; Antonella Napolitano; Duncan B. Richards; Edward T. Bullmore; Pradeep J. Nathan (Psychopharmacology, 2012)

Gene expression changes of interconnected spared cortical neurons 7 days after ischemic infarct of the primary motor cortex in the rat - Edward T. R. Urban; Scott D. Bury; H. Scott Barbay; David J. Guggenmos; Yafeng Dong; Randolph J. Nudo (Molecular and Cellular Biochemistry, 2012)

Incident radiation and the allocation of nitrogen within A rctic plant canopies: implications for predicting gross primary productivity - Lorna E. Street; Gaius R. Shaver; Edward B. Rastetter; Mark T. van Wijk; Brooke A. Kaye; Mathew Williams (Global Change Biology, 2012)
Arctic vegetation is characterized by high spatial variability in plant functional type ( PFT ) composition and gross primary productivity ( P ). Despite this variability, the two main drivers of P in sub‐ A rctic tundra are leaf area index ( L T ) and total foliar nitrogen ( N T ). L T and N T have been shown to be tightly coupled across PFT s in sub‐Arctic tundra vegetation, which simplifies up‐scaling by allowing quantification of the main drivers of P from remotely sensed L T . Our objective was to test the L T – N T relationship across multiple Arctic latitudes and to assess L T as a predictor of P for the pan‐ A rctic. Including PFT ‐specific parameters in models of L T – N T coupling provided only incremental improvements in model fit, but significant improvements were gained from including site‐specific parameters. The degree of curvature in the L T – N T relationship, controlled by a fitted canopy nitrogen extinction co‐efficient, was negatively related to average levels of diffuse radiation at a site. This is consistent with theoretical predictions of more uniform vertical canopy N distributions under diffuse light conditions. Higher latitude sites had higher average leaf N content by mass ( N M ), and we show for the first time that L T – N T coupling is achieved across latitudes via canopy‐scale trade‐offs between N M and leaf mass per unit leaf area ( L M ). Site‐specific parameters provided small but significant improvements in models of P based on L T and moss cover. Our results suggest that differences in L T – N T coupling between sites could be used to improve pan‐Arctic models of P and we provide unique evidence that prevailing radiation conditions can significantly affect N allocation over regional scales.

Incorporating climate change into systematic conservation planning - Craig R. Groves; Edward T. Game; Mark G. Anderson; Molly Cross; Carolyn Enquist; Zach Ferdaña; Evan Girvetz; Anne Gondor; Kimberly R. Hall; Jonathan Higgins; Rob Marshall; Ken Popper; et al. (Biodiversity and Conservation, 2012)

Frontogenesis and Frontal Progression of a Trapping-Generated Estuarine Convergence Front and Its Influence on Mixing and Stratification - Sarah N. Giddings; Derek A. Fong; Stephen G. Monismith; C. Chris Chickadel; Kathleen A. Edwards; William J. Plant; Bing Wang; Oliver B. Fringer; Alexander R. Horner-Devine; Andrew T. Jessup (Estuaries and Coasts, 2012)

Meta-analysis of new genome-wide association studies of colorectal cancer risk - Ulrike Peters; Carolyn M. Hutter; Li Hsu; Fredrick R. Schumacher; David V. Conti; Christopher S. Carlson; Christopher K. Edlund; Robert W. Haile; Steven Gallinger; Brent W. Zanke; Mathieu Lemire; Jagadish Rangrej; et al. (Human Genetics, 2012)

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

Problematic but promising ponds? Palaeoenvironmental evidence from the Norse Eastern Settlement of Greenland - Kevin J. Edwards; J. Edward Schofield; Jason R. Kirby; Gordon T. Cook (Journal of Quaternary Science, 2011)
Pollen‐ and related proxy‐based studies of human–environment interactions during the Norse and later periods within Greenland have primarily involved the investigation of peat, lake and soil deposits, all of which have taphonomic and sampling problems. Many small ponds exist, but they seem to have been relatively ignored in investigations of palaeoecologically based environmental history. To evaluate their usefulness for studies of ecologically related cultural history, especially where sites are in intimate association with the archaeology, a pond in the Norse Eastern Settlement has been examined to investigate three principal questions: (i) Does such a site contain a useful record of environmental history? (ii) Does it offer a record of sufficient resolution and sensitivity for the study of anthropogenic landscape impacts? (iii) Are there any apparent drawbacks to these sequences? Using data obtained from palynological, diatom, sedimentological and radiocarbon analyses, it is concluded that environmental data for each proxy – aside from 14 C dating – are clearly capable of being explained in a reasonably straightforward and compatible manner and fulfil the hopes for the sampling medium. Copyright © 2011 John Wiley & Sons, Ltd.

Altered pain responses in abstinent (±)3,4-methylenedioxymethamphetamine (MDMA, “ecstasy”) users - Una D. McCann; Robert R. Edwards; Michael T. Smith; Kristen Kelley; Michael Wilson; Francis Sgambati; George Ricaurte (Psychopharmacology, 2011)

Genetic architecture of the circadian clock and flowering time in Brassica rapa - P. Lou; Q. Xie; X. Xu; C. E. Edwards; M. T. Brock; C. Weinig; C. R. McClung (Theoretical and Applied Genetics, 2011)

High frequency variability of the Atlantic meridional overturning circulation - B. Balan Sarojini; J. M. Gregory; R. Tailleux; G. R. Bigg; A. T. Blaker; D. R. Cameron; N. R. Edwards; A. P. Megann; L. C. Shaffrey; B. Sinha (Ocean Science, 2011)
We compare the variability of the Atlantic meridional overturning circulation (AMOC) as simulated by the coupled climate models of the RAPID project, which cover a wide range of resolution and complexity, and observed by the RAPID/MOCHA array at about 26° N. We analyse variability on a range of timescales, from five-daily to interannual. In models of all resolutions there is substantial variability on timescales of a few days; in most AOGCMs the amplitude of the variability is of somewhat larger magnitude than that observed by the RAPID array, while the time-mean is within about 10 % of the observational estimate. The amplitude of the simulated annual cycle is similar to observations, but the shape of the annual cycle shows a spread among the models. A dynamical decomposition shows that in the models, as in observations, the AMOC is predominantly geostrophic (driven by pressure and sea-level gradients), with both geostrophic and Ekman contributions to variability, the latter being exaggerated and the former underrepresented in models. Other ageostrophic terms, neglected in the observational estimate, are small but not negligible. The time-mean of the western boundary current near the latitude of the RAPID/MOCHA array has a much wider model spread than the AMOC does, indicating large differences among models in the simulation of the wind-driven gyre circulation, and its variability is unrealistically small in the models. In many RAPID models and in models of the Coupled Model Intercomparison Project Phase 3 (CMIP3), interannual variability of the maximum of the AMOC wherever it lies, which is a commonly used model index, is similar to interannual variability in the AMOC at 26° N. Annual volume and heat transport timeseries at the same latitude are well-correlated within 15–45° N, indicating the climatic importance of the AMOC. In the RAPID and CMIP3 models, we show that the AMOC is correlated over considerable distances in latitude, but not the whole extent of the North Atlantic; consequently interannual variability of the AMOC at 50° N, where it is particularly relevant to European climate, is not well-correlated with that of the AMOC at 26° N, where it is monitored by the RAPID/MOCHA array.

STR/microsatellite primers for the desert tortoise, Gopherus agassizii, and its congeners - T. Edwards; A. Lathrop; A. Ngo; K. Choffe; R. W. Murphy (Conservation Genetics Resources, 2011)

The Role of the Everglades Mangrove Ecotone Region (EMER) in Regulating Nutrient Cycling and Wetland Productivity in South Florida - Victor H. Rivera-Monroy; Robert R. Twilley; Stephen E. Davis; Daniel L. Childers; Marc Simard; Randolph Chambers; Rudolf Jaffe; Joseph N. Boyer; David T. Rudnick; Keqi Zhang; Edward Castañeda-Moya; Sharon M. L. Ewe; et al. (Critical Reviews in Environmental Science and Technology, 2011)

Coordinated approaches to quantify long‐term ecosystem dynamics in response to global change - YIQI LUO; JERRY MELILLO; SHULI NIU; CLAUS BEIER; JAMES S. CLARK; AIMÉE T. CLASSEN; ERIC DAVIDSON; JEFFREY S. DUKES; R. DAVE EVANS; CHRISTOPHER B. FIELD; CLAUDIA I. CZIMCZIK; MICHAEL KELLER; et al. (Global Change Biology, 2011)
Many serious ecosystem consequences of climate change will take decades or even centuries to emerge. Long‐term ecological responses to global change are strongly regulated by slow processes, such as changes in species composition, carbon dynamics in soil and by long‐lived plants, and accumulation of nutrient capitals. Understanding and predicting these processes require experiments on decadal time scales. But decadal experiments by themselves may not be adequate because many of the slow processes have characteristic time scales much longer than experiments can be maintained. This article promotes a coordinated approach that combines long‐term, large‐scale global change experiments with process studies and modeling. Long‐term global change manipulative experiments, especially in high‐priority ecosystems such as tropical forests and high‐latitude regions, are essential to maximize information gain concerning future states of the earth system. The long‐term experiments should be conducted in tandem with complementary process studies, such as those using model ecosystems, species replacements, laboratory incubations, isotope tracers, and greenhouse facilities. Models are essential to assimilate data from long‐term experiments and process studies together with information from long‐term observations, surveys, and space‐for‐time studies along environmental and biological gradients. Future research programs with coordinated long‐term experiments, process studies, and modeling have the potential to be the most effective strategy to gain the best information on long‐term ecosystem dynamics in response to global change.

Trophic level asynchrony in rates of phenological change for marine, freshwater and terrestrial environments - STEPHEN J. THACKERAY; TIMOTHY H. SPARKS; MORTEN FREDERIKSEN; SARAH BURTHE; PHILIP J. BACON; JAMES R. BELL; MARC S. BOTHAM; TOM M. BRERETON; PAUL W. BRIGHT; LAURENCE CARVALHO; TIM CLUTTON‐BROCK; ALISTAIR DAWSON; et al. (Global Change Biology, 2010)
Recent changes in the seasonal timing (phenology) of familiar biological events have been one of the most conspicuous signs of climate change. However, the lack of a standardized approach to analysing change has hampered assessment of consistency in such changes among different taxa and trophic levels and across freshwater, terrestrial and marine environments. We present a standardized assessment of 25 532 rates of phenological change for 726 UK terrestrial, freshwater and marine taxa. The majority of spring and summer events have advanced, and more rapidly than previously documented. Such consistency is indicative of shared large scale drivers. Furthermore, average rates of change have accelerated in a way that is consistent with observed warming trends. Less coherent patterns in some groups of organisms point to the agency of more local scale processes and multiple drivers. For the first time we show a broad scale signal of differential phenological change among trophic levels; across environments advances in timing were slowest for secondary consumers, thus heightening the potential risk of temporal mismatch in key trophic interactions. If current patterns and rates of phenological change are indicative of future trends, future climate warming may exacerbate trophic mismatching, further disrupting the functioning, persistence and resilience of many ecosystems and having a major impact on ecosystem services.

A probabilistic calibration of climate sensitivity and terrestrial carbon change in GENIE-1 - Philip B. Holden; N. R. Edwards; K. I. C. Oliver; T. M. Lenton; R. D. Wilkinson (Climate Dynamics, 2010)

Cancer Patients and Their Companion Animals: Results from a 309-Patient Survey on Pet-Related Concerns and Anxieties During Chemotherapy - Brenda R. Larson; Sherry Looker; Dianne M. Herrera; Edward T. Creagan; Suzanne R. Hayman; Judith S. Kaur; Aminah Jatoi (Journal of Cancer Education, 2010)

Electrophysiological properties of isthmic neurons in frogs revealed by in vitro and in vivo studies - Matthew S. Caudill; Adam T. Eggebrecht; Edward R. Gruberg; Ralf Wessel (Journal of Comparative Physiology A, 2010)

Climatic drivers of hemispheric asymmetry in global patterns of ant species richness - Robert R. Dunn; Donat Agosti; Alan N. Andersen; Xavier Arnan; Carsten A. Bruhl; Xim Cerdá; Aaron M. Ellison; Brian L. Fisher; Matthew C. Fitzpatrick; Heloise Gibb; Nicholas J. Gotelli; Aaron D. Gove; et al. (Ecology Letters, 2009)
Although many taxa show a latitudinal gradient in richness, the relationship between latitude and species richness is often asymmetrical between the northern and southern hemispheres. Here we examine the latitudinal pattern of species richness across 1003 local ant assemblages. We find latitudinal asymmetry, with southern hemisphere sites being more diverse than northern hemisphere sites. Most of this asymmetry could be explained statistically by differences in contemporary climate. Local ant species richness was positively associated with temperature, but negatively (although weakly) associated with temperature range and precipitation. After contemporary climate was accounted for, a modest difference in diversity between hemispheres persisted, suggesting that factors other than contemporary climate contributed to the hemispherical asymmetry. The most parsimonious explanation for this remaining asymmetry is that greater climate change since the Eocene in the northern than in the southern hemisphere has led to more extinctions in the northern hemisphere with consequent effects on local ant species richness.

Changes in fire regimes since the Last Glacial Maximum: an assessment based on a global synthesis and analysis of charcoal data - M. J. Power; J. Marlon; N. Ortiz; P. J. Bartlein; S. P. Harrison; F. E. Mayle; A. Ballouche; R. H. W. Bradshaw; C. Carcaillet; C. Cordova; S. Mooney; P. I. Moreno; et al. (Climate Dynamics, 2008)

Prediction uncertainty of environmental change effects on temperate European biodiversity - Carsten F. Dormann; Oliver Schweiger; P. Arens; I. Augenstein; St. Aviron; Debra Bailey; J. Baudry; R. Billeter; R. Bugter; R. Bukácek; F. Burel; M. Cerny; et al. (Ecology Letters, 2008)
Observed patterns of species richness at landscape scale (gamma diversity) cannot always be attributed to a specific set of explanatory variables, but rather different alternative explanatory statistical models of similar quality may exist. Therefore predictions of the effects of environmental change (such as in climate or land cover) on biodiversity may differ considerably, depending on the chosen set of explanatory variables. Here we use multimodel prediction to evaluate effects of climate, land‐use intensity and landscape structure on species richness in each of seven groups of organisms (plants, birds, spiders, wild bees, ground beetles, true bugs and hoverflies) in temperate Europe. We contrast this approach with traditional best‐model predictions, which we show, using cross‐validation, to have inferior prediction accuracy. Multimodel inference changed the importance of some environmental variables in comparison with the best model, and accordingly gave deviating predictions for environmental change effects. Overall, prediction uncertainty for the multimodel approach was only slightly higher than that of the best model, and absolute changes in predicted species richness were also comparable. Richness predictions varied generally more for the impact of climate change than for land‐use change at the coarse scale of our study. Overall, our study indicates that the uncertainty introduced to environmental change predictions through uncertainty in model selection both qualitatively and quantitatively affects species richness projections.

Effects of atmospheric dynamics and ocean resolution on bi-stability of the thermohaline circulation examined using the Grid ENabled Integrated Earth system modelling (GENIE) framework - T. M. Lenton; R. Marsh; A. R. Price; D. J. Lunt; Y. Aksenov; J. D. Annan; T. Cooper-Chadwick; S. J. Cox; N. R. Edwards; S. Goswami; J. C. Hargreaves; P. P. Harris; et al. (Climate Dynamics, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Millennial timescale carbon cycle and climate change in an efficient Earth system model - T. M. Lenton; M. S. Williamson; N. R. Edwards; R. Marsh; A. R. Price; A. J. Ridgwell; J. G. Shepherd; S. J. Cox (Climate Dynamics, 2006)

Transgenic Plants for Insect Pest Control: A Forward Looking Scientific Perspective - N. Ferry; M. G. Edwards; J. Gatehouse; T. Capell; P. Christou; A. M. R. Gatehouse (Transgenic Research, 2006)

Case Study Part 1: How to Calculate Appropriate Deterministic Long-Term Toxicity to Exposure Ratios (TERs) for Birds and Mammals - R.F. SHORE; D.R. CROCKER; H.R. AKCAKAYA; R.S. BENNETT; P.F. CHAPMAN; M. CLOOK; M. CRANE; I.C. DEWHURST; P.J. EDWARDS; A. FAIRBROTHER; S. FERSON; D. FISCHER; et al. (Ecotoxicology, 2005)

Impairment of specific episodic memory processes by sub-psychotic doses of ketamine: the effects of levels of processing at encoding and of the subsequent retrieval task - Garry D. Honey; Rebekah A. E. Honey; Sam R. Sharar; Danielle C. Turner; Edith Pomarol-Clotet; Dharshan Kumaran; Jon S. Simons; Xiangen Hu; Michael D. Rugg; Edward T. Bullmore; Paul C. Fletcher (Psychopharmacology, 2005)

Comparison of the Pharmacokinetics of Oxycodone and Noroxycodone in Male Dark Agouti and Sprague–Dawley Rats: Influence of Streptozotocin-Induced Diabetes - Lillian Huang; Stephen R. Edwards; Maree T. Smith (Pharmaceutical Research, 2005)

6-Alkylsalicylic Acids and 6-Alkylresorcylic Acids from Ants in the Genus Crematogaster from Brunei - T. H. JONES; S. R. BRUNNER; A. A. EDWARDS; D. W. DAVIDSON; R. R. SNELLING (Journal of Chemical Ecology, 2005)

Bistability of the thermohaline circulation identified through comprehensive 2-parameter sweeps of an efficient climate model - R. Marsh; A. Yool; T. M. Lenton; M. Y. Gulamali; N. R. Edwards; J. G. Shepherd; M. Krznaric; S. Newhouse; S. J. Cox (Climate Dynamics, 2004)

Toxicological Evaluation and QSAR Modelling of Aromatic Amines to Chlorella vulgaris - T. I. Netzeva; J. C. Dearden; R. Edwards; A. D. P. Worgan; M. T. D. Cronin (Bulletin of Environmental Contamination and Toxicology, 2004)

Effects of Direct Ocean CO2 Injection on Deep-Sea Meiofauna - James P. Barry; Kurt R. Buck; Chris F. Lovera; Linda Kuhnz; Patrick J. Whaling; Edward T. Peltzer; Peter Walz; Peter G. Brewer (Journal of Oceanography, 2004)

The Chemistry of Exploding Ants, Camponotus SPP. (Cylindricus COMPLEX) - T. H. Jones; D. A. Clark; A. A. Edwards; D. W. Davidson; T. F. Spande; R. R. Snelling (Journal of Chemical Ecology, 2004)

West Nile virus: pending crisis for greater sage‐grouse - David E. Naugle; Cameron L. Aldridge; Brett L. Walker; Todd E. Cornish; Brendan J. Moynahan; Matt J. Holloran; Kimberly Brown; Gregory D. Johnson; Edward T. Schmidtmann; Richard T. Mayer; Cecilia Y. Kato; Marc R. Matchett; et al. (Ecology Letters, 2004)
Scientists have feared that emerging infectious diseases could complicate efforts to conserve rare and endangered species, but quantifying impacts has proven difficult until now. We report unexpected impacts of West Nile virus (WNv) on radio‐marked greater sage‐grouse ( Centrocercus urophasianus ), a species that has declined 45–80% and is endangered in Canada and under current consideration for federal listing in the US. We show that WNv reduced late‐summer survival an average of 25% in four radio‐marked populations in the western US and Canada. Serum from 112 sage‐grouse collected after the outbreak show that none had antibodies, suggesting that they lack resistance. The spread of WNv represents a significant new stressor on sage‐grouse and probably other at‐risk species. While managing habitat might lessen its impact on sage‐grouse populations, WNv has left wildlife and public health officials scrambling to address surface water and vector control issues in western North America.

Nitrogen Leaching and Denitrification in Continuous Corn as Related to Residue Management and Nitrogen Fertilization - Hero T. Gollany; Jean-Alex E. Molina; C. Edward Clapp; Raymond R. Allmaras; Milegua F. Layese; John M. Baker; H. H. Cheng (Environmental Management, 2004)

Assessing anthropogenic impact on Mediterranean sand dunes from aerial digital photography - R. H. F. Curr; A. Koh; E. Edwards; A. T. Williams; P. Davies (Journal of Coastal Conservation, 2000)

Characterisation and analysis of microsatellite loci in a mangrove species, Avicennia marina (Forsk.) Vierh. (Avicenniaceae) - T. L. Maguire; K. J. Edwards; P. Saenger; R. Henry (Theoretical and Applied Genetics, 2000)

Pollen‐based biomes for Beringia 18,000, 6000 and 0 14 C yr bp † - M. E. Edwards; P. M. Anderson; L. B. Brubaker; T. A. Ager; A. A. Andreev; N. H. Bigelow; L. C. Cwynar; W. R. Eisner; S. P. Harrison; F.‐S. Hu; D. Jolly; A. V. Lozhkin; et al. (Journal of Biogeography, 2000)
The objective biomization method developed by Prentice et al . (1996) for Europe was extended using modern pollen samples from Beringia and then applied to fossil pollen data to reconstruct palaeovegetation patterns at 6000 and 18,000 14 C yr bp . The predicted modern distribution of tundra, taiga and cool conifer forests in Alaska and north‐western Canada generally corresponds well to actual vegetation patterns, although sites in regions characterized today by a mosaic of forest and tundra vegetation tend to be preferentially assigned to tundra. Siberian larch forests are delimited less well, probably due to the extreme under‐representation of Larix in pollen spectra. The biome distribution across Beringia at 6000 14 C yr bp was broadly similar to today, with little change in the northern forest limit, except for a possible northward advance in the Mackenzie delta region. The western forest limit in Alaska was probably east of its modern position. At 18,000 14 C yr bp the whole of Beringia was covered by tundra. However, the importance of the various plant functional types varied from site to site, supporting the idea that the vegetation cover was a mosaic of different tundra types.

Abstracts of presentations on selected topics at the XIVth international plant protection congress (IPPC) July 25–30, 1999 - R. Hull; H. A. Kuiper; Maryvon Y. Noordam; Marjorie A. Hoy; Jenny S. Cory; A. C. Fereres; P. Gonzalez; F. Meins; Y. Elkind; Benedicte Charrier; P. Meyer; M. Metzlaff; et al. (Phytoparasitica, 1999)

Essential versus alternative foods of insect predators: benefits of a mixed diet - Edward W. Evans; Adam T. Stevenson; Douglas R. Richards (Oecologia, 1999)

Partition Constants and Adsorption/Desorption Hysteresis for Volatile Organic Compounds on Soil from a Louisiana Superfund Site - Kalliat T. Valsaraj; Raghava R. Kommalapati; Edward D. Robertson; W. D. Constant (Environmental Monitoring and Assessment, 1999)

Identification of a microsatellite on chromosomes 6B and a STS on 7D of bread wheat showing an association with preharvest sprouting tolerance - J. K. Roy; M. Prasad; R. K. Varshney; H. S. Balyan; T. K. Blake; H. S. Dhaliwal; H-Singh; K. J. Edwards; P. K. Gupta (Theoretical and Applied Genetics, 1999)

Parametric and Nonparametric Nonlinear System Identification of Lung Tissue Strip Mechanics - Huichin Yuan; David T. Westwick; Edward P. Ingenito; Kenneth R. Lutchen; Béla Suki (Annals of Biomedical Engineering, 1999)

Abundance and polymorphism of microsatellite markers in the tea tree (Melaleuca alternifolia, Myrtaceae) - M. Rossetto; A. McLauchlan; F. C. L. Harriss; R. J. Henry; P. R. Baverstock; L. S. Lee; T. L. Maguire; K. J. Edwards (Theoretical and Applied Genetics, 1999)

Pollination of sevenPlectranthus spp. (Lamiaceae) in southern Natal, South Africa - C. J. Potgieter; T. J. Edwards; R. M. Miller; J. Van Staden (Plant Systematics and Evolution, 1999)

The biosynthetic relationship between littorine and hyoscyamine in transformed roots of Datura stramonium - I. Zabetakis; R. Edwards; John T. G. Hamilton; D. O'Hagan (Plant Cell Reports, 1998)

Correlation between Waardenburg syndrome phenotype and genotype in a population of individuals with identified PAX3 mutations - Anita L. DeStefano; L. Adrienne Cupples; Kathleen S. Arnos; J. H. Jr. Asher; Clinton T. Baldwin; Susan Blanton; Melisa L. Carey; Elias O. da Silva; T. B. Friedman; Jacquie Greenberg; Anil K. Lalwani; Aubrey Milunsky; et al. (Human Genetics, 1998)

The Pharmacokinetics and Electroencephalogram Response of Remifentanil Alone and in Combination with Esmolol in the Rat - Sam H. Haidar; J. Edward Moreton; Zhongming Liang; John R Hoke; Keith T. Muir; Natalie D. Eddington (Pharmaceutical Research, 1997)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

The amino acid sequence of the light chain of Acanthamoeba myosin IC - ZHEN-YUAN WANG; JUN SAKAI; PAUL T. MATSUDAIRA; IVAN C. BAINES; JAMES R. SELLERS; JOHN A. HAMMER III; EDWARD D. KORN (Journal of Muscle Research and Cell Motility, 1997)

High level production of potyvirus-like particles in insect cells infected with recombinant baculovirus - S. J. Edwards; M. B. Hayden; R. C. Hamilton; J. A. Haynes; I. T. Nisbet; M. N. Jagadish (Archives of Virology, 1994)